Phosphor Particle Coating

JP7633290B2Active Publication Date: 2025-02-19LUMILEDS LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022579733
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-05
Filing Date
2021-06-29
Publication Date
2025-02-19
Estimated Expiration
2041-06-29

Smart Images

  • Figure 0007633290000008
    Figure 0007633290000008
  • Figure 0007633290000009
    Figure 0007633290000009
  • Figure 0007633290000010
    Figure 0007633290000010
Patent Text Reader

Abstract

In the present invention, a method is provided for providing a luminescent particle (100) having a hybrid coating. The method includes the steps of: (i) providing a light-emitting core (102) having a primer layer (105) thereon; (ii) providing a main ALD coating layer (120) on the primer layer (105) by applying a main atomic layer deposition process, the main ALD coating layer (120) having a multilayer (1120) having two or more layers (1121) with different chemical compositions, in which the metal oxide precursor in the main atomic layer deposition process is selected from the group of metal oxide precursors including Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V; and (iii) providing a main sol-gel coating layer (130) on the main ALD-coating layer (120) by applying a main sol-gel coating process, the main sol-gel coating layer (130) having a different chemical composition from one or more layers (1121) of the multilayer (1120).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to U.S. Patent Application No. 16 / 915,422, filed June 29, 2020, and entitled "Phosphor Particle Coating," and European Patent Application No. 20189538.0, filed August 5, 2020, and entitled "Phosphor Particle Coating," which are hereby incorporated by reference in their entireties.

[0002] The present application relates to a method for providing coated luminescent materials, such phosphor materials, and lighting devices comprising such luminescent materials for wavelength conversion. [Background technology]

[0003] Coating of luminescent materials is known in the art. For example, WO2014 / 128676 describes coated luminescent particles, luminescence converter elements, light sources, luminaires, and methods for producing coated luminescent particles. The coated luminescent particles have a luminescent particle, a first coating layer, and a second coating layer. The luminescent particle has a luminescent material that absorbs light in a first spectral region and converts the absorbed light into light in a second spectral region. The luminescent material is sensitive to moisture. The first coating layer forms a first barrier against moisture and has a metal oxide or nitride, phosphide, sulfide-based coating. The second coating layer forms a second barrier against moisture and has a silicon-based polymer or a continuous layer of one of the materials AIPO4, SiO2, Al2O3, and LaPO4. The first and second coating layers are light-transmitting. The first coating layer encapsulates the luminescent particles, and the second coating layer, together with the first coating layer, encapsulates the luminescent particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2014 / 128676 Summary of the Invention [Problem to be solved by the invention]

[0005] Moisture-sensitive luminescent powder materials can be coated with a layer of amorphous or glassy material to slow down the rate of decomposition due to moisture attack. The coating can be applied by depositing the material on the particle surface by reacting inorganic precursors dissolved in suspension (e.g., sol-gel method) or by deposition from the gas phase (e.g., chemical vapor deposition or atomic layer deposition (ALD) methods).

[0006] Atomic layer deposition can be a suitable method for depositing thin conformal coatings of various inorganic materials onto powder particles. The ALD layers can be extremely dense, conformal, and substantially impermeable to gases such as water vapor and oxygen.

[0007] ALD processes further allow the deposition of multiple thin layers (nanolaminates) of different inorganic materials, each providing different physical properties to the layer (e.g. moisture resistance, optical transparency, stress resistance, elasticity, etc.) These properties may be different for the different (nano)layers.

[0008] The sol-gel process is suitable for providing (relatively) thick layers that can provide mechanical protection to the material on which they are coated.

[0009] Known coated luminescent particles may exhibit one or more problems, such as decomposition of the luminescent material by moisture or, for example, solvents, decomposition as a result of high temperatures, mechanical instability during processing of the luminescent particles, etc. Furthermore, many of the known coating processes have one or more problems, such as agglomeration, reduced quantum efficiency of the coated luminescent material (relative to the uncoated material), non-conformal coatings, etc.

[0010] In the sol-gel coating process, the properties of the luminescent material alone may not be sufficient. Also, moisture-sensitive luminescent particles that only include an ALD coating may not be durable enough when exposed to mechanical stress. Furthermore, moisture-sensitive luminescent particles with a sol-gel coating in combination with an ALD coating configured on top of the sol-gel coating may provide luminescent particles with reduced decomposition rates due to moisture attack at relatively harsh conditions, such as temperatures up to 60° C. and 90% relative humidity. However, at higher temperatures, such as those encountered in high-power LED applications, such as flash and vehicle applications, alternative coating structures may be preferred. Furthermore, ALD layers exhibit inherent (tensile) stresses, which may increase with increasing layer thickness. ALD coatings are preferably provided as thin layers. However, deposition of particularly thin ALD layers is prone to surface contamination. Possible contamination at the surface of the coated particles may cause pinholes or other irregularities in the (thin) ALD layer.

[0011] Thus, one aspect of the present invention is to provide an alternative coating process, preferably one that at least partially alleviates one or more of the aforementioned problems. Another aspect of the present invention is to provide an alternative luminescent material, preferably one that at least partially alleviates one or more of the aforementioned problems. In yet another aspect, the present invention is to provide a lighting device having the luminescent material, preferably one that at least partially alleviates one or more of the aforementioned problems.

[0012] The present invention may be included to overcome or ameliorate at least one of the problems in the prior art, or to provide a useful alternative. [Means for solving the problem]

[0013] In particular, the present invention proposes in an embodiment a coating structure comprising at least two layers, in particular at least three layers, arranged around the light-emitting core. The different layers may be selected to have different functions. The coating structure may in particular have a primer layer, a coating layer provided by atomic layer deposition ("ALD coating layer"), and a coating layer provided by a sol-gel (deposition) process ("sol-gel coating layer"). The primer layer may promote good adhesion between the surfaces and promote the deposition of a thin ALD coating layer. The ALD coating layer may shield the light-emitting core from undesirable gases such as water vapor and oxygen or further chemicals. The sol-gel coating may provide mechanical protection for the light-emitting core and the ALD coating layer.

[0014] Thus, the present application provides a method for hybrid coating of luminescent powder materials, which comprises the steps of depositing a coating layer on a primer layer (surface of the luminescent core) by applying an ALD process, and depositing a sol-gel layer by applying a sol-gel type process to obtain a uniformly coated luminescent particle. In this method, luminescent particles with a hybrid coating can be provided.

[0015] Thus, in a first aspect, the present invention provides a method for providing a luminescent particle having a hybrid coating. In one embodiment, the method comprises inter alia (i) providing a luminescent core ("core") (or a "primer layer" comprising a luminescent core) comprising a primer layer ("primer coating" or "primer coating layer") on the luminescent core. The method further comprises (ii) providing a (main) atomic layer deposition coating layer ("(main) ALD coating layer" or "(main) ALD coating" or "(main) ALD layer") on the primer layer. In one embodiment, the (main) ALD coating layer is provided on the primer layer, in particular comprising the light emitting core. The method further comprises (iii) providing a (main) sol-gel coating layer ("(main) sol-gel coating" or "(main) sol-gel layer") on the (main) ALD coating layer. Furthermore, the (main) ALD coating layer may be provided on the primer layer by application of a (main) atomic layer deposition process ("(main) ALD process"). Furthermore, in certain embodiments, the (main) ALD coating layer may comprise a multilayer (or "stack") having two or more layers with different chemical compositions. In another particular embodiment, in the (main) atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors comprising Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si). A (main) sol-gel coating layer is provided on top of the (main) ALD coating layer, in particular by application of a (main) sol-gel coating process. In another embodiment, the main sol-gel coating layer may have a different chemical composition than one or more layers of the multilayer.

[0016] In yet another embodiment, the present invention provides a luminescent material comprising luminescent particles obtained by such a method. In particular, in another embodiment, the present invention provides a luminescent material comprising luminescent particles and a (main) ALD (i.e. atomic layer deposition) coating layer, in particular a (main) ALD (i.e. atomic layer deposition) coating layer comprising a multilayer having two or more layers of different chemical composition. Here, the luminescent particles have a luminescent core comprising a primer layer on the luminescent core, in particular the primer layer has a primer layer thickness (d1) in the range of 0.1-10 nm, in particular 0.1-7 nm, such as 0.1-5 nm or 0.1-4 nm, and the primer layer has a chemical composition different from the chemical composition of the core. In one embodiment, the (main) ALD coating layer has an ALD coating layer thickness (d2) in the range of 5-250 nm, such as in the range of 5-100 nm, in particular 5-50 nm, in particular 10-50 nm, in particular 20-50 nm, the multilayer comprises one or more layers comprising one or more oxides of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si), and one or more of the two or more layers of the multilayer have a chemical composition different from the chemical composition of the primer layer, and further, in an embodiment comprising a (main) sol-gel coating layer, the (main) sol-gel coating layer has a (main) sol-gel coating layer thickness (d3) in the range of 50-700 nm, such as in the range of 50-600 nm, in particular 75-500 nm, in particular 100-500 nm. In another embodiment, the (primary) sol-gel coating layer has a different chemical composition than the (primary) ALD coating layer, in particular one or more of the two or more layers of the multilayer.More particularly, the (primary) ALD coating layer is disposed between the primer layer and the (primary) sol-gel layer.

[0017] In the present invention, luminescent particles and luminescent materials, i.e. luminescent materials comprising these (hybrid-coated) particles, may be provided, which have a significantly reduced decomposition rate as a result of moisture attack. The coating of the luminescent particles may exhibit improved moisture barrier properties. The coating further provides improved chemical and mechanical stability, allowing the integration of luminescent particles (phosphors), for example moisture-sensitive luminescent particles (phosphors), in high-power products for flash and vehicle applications, which are subject to high stress conditions, such as operating temperatures of up to 85°C at relatively high relative humidity (relative humidity above 80%). Such luminescent materials provide relatively stable luminescent materials, with quantum efficiencies close to or equal to those of virgin (uncoated) luminescent materials, and significantly higher and superior stability to water and / or (humid) air than uncoated or hybrid-coated luminescent particles.

[0018] In one embodiment, the present invention provides, inter alia, a method for providing a luminescent particle comprising a hybrid coating, the method comprising the steps of: (i) providing a luminescent core comprising a primer layer on the luminescent core; (ii) providing a main ALD coating layer on the primer layer by application of a main atomic layer deposition process, the main ALD coating layer having a multilayer having two or more layers having different chemical compositions, in which the metal oxide precursor is selected from the group of metal oxide precursors comprising Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si); and (iii) providing a main sol-gel coating layer on the main ALD coating layer by application of a main sol-gel coating process, the main sol-gel coating layer having a different chemical composition from one or more layers of the multilayer. In particular, in the principal atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si).

[0019] The starting material is therefore a particulate luminescent material or a luminescent material configured into a particulate form. Also, in particular, the luminescent core is a particulate core or a luminescent (core) material that has been granulated. The core may be an essentially (virgin) luminescent particle / core, i.e. an uncoated coated / untreated luminescent particle. The luminescent particles of the particulate luminescent material (in particular, the core) are coated as described herein. The terms "luminescent particle", "luminescent core" and similar terms refer in particular to particles and / or cores that emit light under excitation by UV and / or blue radiation (source radiation, see below). Also in this application, the term "luminescent particle" may be used to refer to a "luminescent core". Furthermore, in this application, the coated luminescent particle is also referred to as a "luminescent particle". It is clear from the context whether the term "luminescent particle" refers to an uncoated core or, for example, to a luminescent particle that includes a hybrid coating or to a luminescent particle that includes only one or more layers of a hybrid coating.

[0020] The luminescent core (before applying the ALD coating process) in particular has a primer layer on (a surface of) the luminescent core. Here, a luminescent core comprising a primer layer (on the luminescent core) is also referred to as "primer layer with luminescent core". In one embodiment, the virgin (core) material (already) has a primer layer. In one embodiment, for example, the core may have an oxide-containing surface. In another embodiment, a primer layer may be provided on the virgin (core) material, in particular in the method of the invention. Thus, in another embodiment, the method may comprise a step of providing a primer layer on the core (to provide a luminescent core with a primer layer on the luminescent core) (see below).

[0021] The primer layer does not necessarily have to be entirely conformal with the core. In particular, the primer layer may be evenly distributed on top of (the surface of) the light-emitting core. However, in an embodiment, the primer layer may not completely cover the surface of the core. In an embodiment, the primer layer may cover at least 50%, in particular at least 75%, such as at least 90%, or in particular at least 95% or more, or even more in particular at least 99% of the surface of the core (as described in more detail below). The primer layer may be configured in particular to facilitate the deposition of the main ALD coating layer. The primer layer may act as a nucleation or seed layer for the main ALD coating layer.

[0022] The main ALD coating layer is provided on the primer layer. Thus, in one embodiment, the ALD coating layer contacts the surface of the light-emitting core at a first location of the light-emitting core, which includes the primer layer, and the ALD coating layer may contact the primer layer at another location. The main ALD coating layer may include a multilayer, if necessary. However, the multilayer of the main ALD coating layer is all ALD layers. This layer is therefore referred to as a (main) ALD (coating) layer (and thus optionally including an ALD multilayer). In particular, the main ALD coating layer includes a multilayer having two or more layers (with different chemical compositions). See below. The main ALD coating layer in particular includes at least one or more aluminum oxide (in particular Al2O3) coating layers.

[0023] Likewise, the main sol-gel coating layer may comprise a multilayer, if necessary. However, the (multilayer) layers of the main sol-gel coating layer are all sol-gel layers. This coating layer is therefore also referred to as a (main) sol-gel (coating) layer (and thus optionally including a sol-gel multilayer). Furthermore, in particular, the main sol-gel coating layer is provided on the main ALD coating layer without an intermediate layer. The main sol-gel coating layer in particular comprises a silicon oxide, in particular SiO2. Examples of multilayers include, for example, a silicon oxide layer made of SiO2 and Al2O 3-x (OH) 2xSiO2-Al2O, such as a stack of three or more (sol-gel) layers with alternating (0≦x≦3) 3-x (OH) 2x (Sol-gel) multilayers (0≦x≦3) are included. If necessary, on the main sol-gel coating layer further coating layers may be provided (see below for details).

[0024] In particular, both the primary ALD coating layer and the primary sol-gel coating layer can independently comprise a metal oxide, although one or more of these layers can include a hydroxide, if desired. Additionally, the primary ALD coating layer and the primary sol-gel coating layer can independently comprise a mixed oxide layer. Additionally, the coating layers need not be perfectly stoichiometric oxides, as is known in the art.

[0025] In one embodiment, the primer layer (also) comprises a sol-gel coating layer (provided by application of a sol-gel process). Here, in particular, such a sol-gel coating layer may be indicated as a primary sol-gel coating layer to distinguish it from the main sol-gel coating layer. In one embodiment, the primary sol-gel coating layer comprises a metal oxide and, if necessary, a hydroxide, as described herein with respect to the main sol-gel coating layer. Furthermore, the main sol-gel coating layer may be provided in particular as described with respect to the main sol-gel coating layer. As shown below, the sol-gel process is described below. In particular, the primary sol-gel coating layer may be provided (comprising a composition) as described with respect to the main sol-gel coating.

[0026] In another embodiment, the primer layer may (further) comprise an oxide-containing layer. In an embodiment, the oxide-containing layer is provided by application of a chemical cleaning process to the light-emitting core (see below). The chemical cleaning process may provide a layer on the light-emitting core, in particular as a result of cleaning. Thus, in one embodiment, the cleaned layer comprises an oxide-containing layer. The primer layer may in particular function as a nucleation or seed layer for the main ALD coating layer. However, the primer layer may be structurally different for the various embodiments. As mentioned above, in one embodiment, the primer layer is in particular constituted by an oxide-containing layer (or an oxide-rich layer) (at the surface of the light-emitting core). In another embodiment, the primer layer comprises in particular a cleaned layer. In another embodiment, the primer layer is in particular constituted by a primary sol-gel coating layer. In another particular embodiment, the primer layer comprises a cleaned layer and a primary sol layer.

[0027] In particular, the primary sol-gel coating layer may be provided after the chemical cleaning process (if the core is subjected to a chemical cleaning step), in particular the primary sol-gel coating may be provided on the cleaned layer (in particular the oxide-containing layer). Furthermore, in such an embodiment, the primary sol-gel coating layer may contact the cleaned layer at a first location of the luminescent core. The primary sol-gel coating may contact the surface of the luminescent core at another location of the luminescent core. Thus, in one embodiment, the primer layer comprises an oxide-containing layer and a primary sol-gel layer, in particular the oxide-containing layer is disposed on the surface of the core (at least a portion of the primary sol-gel coating layer is disposed on the oxide-containing layer).

[0028] As mentioned above, in one embodiment, the core location may not be covered by a primary layer (particularly one or more of the oxide-containing layer and the primary sol-gel coating layer). Thus, in one embodiment, a main ALD coating layer may be in contact (provided) with a primary sol-gel coating layer at one location of the light-emitting core, and a main ALD coating layer may be in contact (provided) with a surface of the core at another location of the light-emitting particle. In yet another embodiment, the main ALD coating may be in contact (provided) with a washed layer at yet another location of the light-emitting particle.

[0029] In general, the thickness of the primer layer is less than the thickness of the main sol-gel layer, in particular less than the thickness of the main ALD coating layer. Furthermore, in particular, the thickness of the main sol-gel coating layer is generally greater than the thickness of the ALD coating layer. The thickness of the primer layer is in particular 10 nm or less, for example 7 nm or less, in particular 5 nm or less, in particular 4 nm or less. In one embodiment, the thickness of the primer layer is at least 0.1 nm, such as at least 0.2 nm, at least 0.5 nm, in particular at least 1 nm. The thickness of the primary layer may in particular be the result of the thickness of the primary sol-gel coating layer. Thus, in particular, the primary sol-gel coating layer may be 10 nm or less, for example 7 nm or less, in particular 5 nm or less, for example 4 nm or less. In one embodiment, the oxide-containing layer may be less than 1 nm thick. In one embodiment, the primer layer has a primer layer thickness (d1) in the range of 0.1 to 5 nm. In another embodiment, the primer layer comprises a primary sol-gel layer provided by application of a primary sol-gel coating process. In particular, the thickness of the main sol-gel coating layer may be at least 10 times, such as at least 50 times, in particular at least 100 times, thicker than the thickness of the primary layer.

[0030] Also in particular, the thickness of the main sol-gel coating layer is generally greater than the thickness of the main ALD coating layer, e.g., at least 1.2, e.g., at least 1.5, at least 2 times, or at least 4 times, at least 5 times, or at least 10 times greater (than the thickness of the main ALD coating layer).

[0031] In a particular embodiment, the method of the present invention comprises the steps of (i) providing a primer layer on top of the core, in particular having a primer layer thickness (d1) in the range of 0.1 to 10 nm, in particular 0.1 to 7 nm, such as for example 0.1 to 5 nm or 0.1 to 4 nm (providing a primer layer comprising a light-emitting core); and (ii) depositing a thickness (d1) in the range of 3 to 250 nm, for example 5 to 250 nm, in particular 5 to 100 nm, in particular on the primer layer (in particular the primer layer comprising a light-emitting core) by applying a principal atomic layer deposition process. providing a main ALD coating layer having a main ALD coating layer thickness (d2) of 5 to 50 nm, for example 10 to 50 nm, in particular 20 to 50 nm, and in particular (iii) providing on the main ALD coating layer by application of a main sol-gel process a main sol-gel coating layer having a main sol-gel coating layer thickness (d3) in the range of 50 to 700 nm, for example 50 to 600 nm, in particular 75 to 500 nm, in particular 100 to 500 nm.

[0032] In particular, the primer layer has a primer layer thickness (d1) in the range of 0.1-10 nm, in particular 0.1-7 nm, for example 0.1-5 nm or 0.1-4 nm. Also, the main ALD coating layer has a main ALD coating layer thickness (d2) in the range of 3-250 nm, for example 5-250 nm, in particular 5-100 nm, in particular 5-50 nm, for example 10-50 nm, in particular 20-50 nm. In particular, the main sol-gel coating layer has a main sol-gel coating layer thickness (d3) in the range of 50-700 nm, for example 50-600 nm, in particular 75-500 nm, for example 100-500 nm.

[0033] Thus, in one embodiment, as described above, the luminescent particle comprises a luminescent core, a primer layer having a primer layer thickness (d1) in the range of 0.1-10 nm, in particular 0.1-7 nm, such as 0.1-5 nm or 0.1-4 nm, a main ALD coating layer having a main ALD coating layer thickness (d2) in the range of 3-250 nm, such as 5-250 nm, in particular 5-100 nm, in particular 5-50 nm, such as 10-50 nm, in particular 20-50 nm, and a main sol-gel coating layer having a main sol-gel coating layer thickness (d3) in the range of 50-700 nm, such as 50-600 nm, in particular 75-500 nm, such as 100-500 nm.

[0034] In one embodiment, the primer layer at least partially seals the surface of the luminescent core. In another embodiment, the main ALD coating seals the primer layer. In another embodiment, the main sol-gel coating seals the main ALD coating layer. In yet another embodiment, the other ALD coating layer seals the main sol-gel coating layer (see below). Thus, the hybrid coating may have a main ALD coating layer and a main sol-gel coating layer, in particular a primer layer, a main ALD coating layer and a main sol-gel coating layer. In particular, the primer layer is in particular disposed between the surface of the luminescent core and the main ALD coating layer. The main ALD coating layer is in particular disposed between the main sol-gel coating layer and the primer layer.

[0035] In another embodiment, the luminescent particles may have a further coating layer disposed on the main sol-gel coating layer. In another embodiment, the hybrid coating further comprises a further coating layer disposed on the main sol-gel coating layer. The further coating layer may in particular comprise a further ALD coating layer sealing the main sol-gel coating. Thus, in one embodiment, the luminescent particles (further) comprise a further ALD coating layer disposed on the main sol-gel coating layer. The further ALD coating layer in particular has a further ALD coating layer thickness (d4) in the range of 1-100 nm, for example 5-75 nm, in particular 10-75 nm, in particular 10-50 nm. Furthermore, in particular, the further ALD coating layer has a chemical composition different from the chemical composition of the main sol-gel coating layer.

[0036] Thus, in a particular embodiment, the method comprises the step of (iv) providing a further ALD coating layer on the main sol-gel coating by application of a further atomic layer deposition process (in particular to provide a further ALD coated luminescent particle), in particular the further ALD coating layer has a further ALD coating layer thickness (d4) in the range of 1-100 nm, for example 5-75 nm, in particular 10-75 nm, in particular 10-50 nm, in particular the further ALD coating layer has a chemical composition different from that of the main sol-gel coating layer. The further ALD coating layer may be provided by an ALD process as described herein, in particular with respect to the main ALD layer. The further ALD layer may (also) comprise a multilayer. The further ALD layer may further have a composition (and / or (metal) oxide) as described in particular with respect to the main ALD layer. In an embodiment, the further ALD coating layer may comprise one or more oxides of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V, and optionally Si.

[0037] Here, the term "thickness" is used in relation to coatings and layers. This term particularly relates to the average thickness of the coating over the entire surface covered by the respective layer. For example, the primary layer may not completely cover the surface of the core, and the (local) thickness of the primer layer may be substantially zero at the location of the surface core. At other locations of the surface, the maximum (local) thickness of the primer layer may be 3 nm. Then, for example, the primer layer thickness may range from greater than 0 to less than 3 nm. Also, if a (coating) layer completely covers the core or another coating layer, the thickness may vary locally. In particular, for example, in sol-gel processes, coating layers are provided that have a somewhat pocked shape or may, for example, contain one or more small pinholes. The layer thicknesses described in this application are therefore in particular average layer thicknesses. However, at least for the primer layer, the main sol-gel coating layer, the main ALD coating layer and the further ALD coating layer (if present), at least 50% and more particularly at least 80% of the area of ​​the respective layers have such indicated layer thickness. In particular, this indicates that at least 50% of the area of ​​such layer is characterized by such thickness.

[0038] The luminescent core of interest may in principle comprise each type of (virgin) luminescent particle or particle material. However, of particular interest are types of luminescent particle materials (particles) that are not very stable in air or water or in a humid environment, such as (oxo)sulfides, (oxo)nitrides, etc. Thus, in one embodiment, the luminescent core (and the luminescent particle comprising the luminescent core) comprises one or more of nitride luminescent materials, oxynitride luminescent materials, halide luminescent materials, oxohalide luminescent materials, sulfide luminescent materials, and oxosulfide luminescent materials. Additionally or alternatively, the luminescent core (luminescent particle) may comprise a selenide luminescent material. Thus, the term "luminescent core" (and "luminescent particle") may represent a combination of particle materials of different types of luminescent materials. In one embodiment, the luminescent core may in particular comprise a plurality of particulate luminescent materials / luminescent particles.

[0039] In certain embodiments, the luminescent core (or the material of the luminescent core) may be selected from the following group of luminescent material systems: MLiAl3N4:Eu (M = Sr, Ba, Ca, Mg), MLi2Al2O2N2:Eu (M = Ba, Sr, Ca), M2SiO4:Eu (M = Ba, Sr, Ca), MSe 1-x S x :Eu(M=Sr, Ca, Mg), MA2S4:Eu(M=Sr, Ca, A=Al, Ga), M2SiF6:Mn(M=Na, K, Rb), MSiAlN3:Eu(M=Ca, Sr), M8Mg(SiO4)4Cl 2:Eu(M=Ca, Sr), M3MgSi2O8:Eu(M=Sr, Ba, Ca), MSi2O2N2:Eu(M=Ba, Sr, Ca), MLi3SiO4:Eu(M=Li, Na, K, Rb, Cs), M2Si 5-x A1 x O x N 8-x :Eu (M = Sr, Ca, Ba). However, there is growing interest in other systems protected by hybrid coatings. Also, particle / particle material combinations of two or more different luminescent materials may be applied, for example a green or yellow luminescent material combined with a red luminescent material.

[0040] As is known in the art, a term such as "M=Sr, Ba, Ca, Mg" indicates that M includes one or more of Sr, Ba, Ca, and Mg. For example, when referring to MSiAlN3:Eu (M=Ca, Sr), this can be, by way of example, CaSiAlN3:Eu, or SrSiAlN3:Eu, or Ca 0.8 Sr 0.2 SiAlN3:Eu, etc. Furthermore, the general formula "MLiAl3N4:Eu (M = Sr, Ba, Ca, Mg)" is equivalent to the general formula (Sr, Ba, Ca, Mg)LiAl3N4:Eu. Furthermore, for reasons of clarity, for example, "The luminescent material is (Ml)Li d Mg a Al bN4: Eu, 0≦a≦4; 0≦b≦4; 0≦d≦4; and M1 includes one or more of the group consisting of Ca, Sr, and Ba; (M2) Li2Al 2-z S z O 2-z N 2+z The general formula "(Ml)LiAl3N4:Eu,Ml=Sr,Ba,Ca" in sentences such as "(Ml)LiAl3N4:Eu,Ml=Sr,Ba,Ca" is used, for example, when two or more groups are represented by different elements. Furthermore, M1, M2, etc. may refer to one or more (respective) elements. In the above given example, for example, in one embodiment, M1 may be Sr, Ba, or Ca. In another embodiment, Ml may be a combination of Sr and Ba, or, for example, Sr and Ca, or Sr, Ba, and Ca, etc. Furthermore, the elements may be present in any ratio, in particular, for example, 20% Sr, 20% Ca, and 50% Ba, or 10% Ba and 90% Sr, etc. Similarly, this applies to the general formulas of other inorganic luminescent materials described in this application.

[0041] In another particular embodiment, the light emitting core may be selected from the following group of light emitting material systems: M 1-x-y-z Z z A a B b C c D d E e N 4-n O n :ES x ,Re y where M=Ca (calcium), Sr (strontium), and Ba (barium); Z is selected from monovalent Na (sodium), K (potassium), and Rb (rubidium); A is selected from the group consisting of divalent Mg (magnesium), Mn (manganese), Zn (zinc), and Cd (cadmium), in particular, A is selected from divalent Mg (magnesium), Mn (manganese), and Zn (zinc), and in particular, is selected from divalent Mg (magnesium) and Mn (manganese). B is selected from the group consisting of trivalent B (boron), Al (aluminum), and Ga (gallium). C is selected from the group consisting of tetravalent Si (silicon), Ge (germanium), Ti (titanium), and Hf (hafnium). D is selected from the group consisting of monovalent Li (lithium) and Cu (copper). E is selected from the group consisting of P (elemental phosphorus), V (vanadium), Nb (niobium), and Ta (tantalum). ES is selected from the group consisting of divalent Eu (europium), Sm (samarium), and ytterbium, in particular, is selected from the group consisting of divalent Eu and Sm. RE is selected from the group consisting of trivalent Ce (cerium), Pr (praseodymium), Nd (neodymium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), and Tm (thulium), where 0 ≦ x ≦ 0.2; 0 ≦ y ≦ 0.2; 0 < x + y ≦ 0.4, 0 ≦ z < 1, 0 ≦ n ≦ 0.5, 0 ≦ a ≦ 4 (for example 2 ≦ a ≦ 3); 0 ≦ b ≦ 4; 0 ≦ c ≦ 4; 0 ≦ d ≦ 4; 0 ≦ e ≦ 4; a + b + c + d + e = 4; and 2a + 3b + 4c + d + 5e = 10 - y - n + z. In particular, z ≦ 0.9, for example z ≦ 0.5. In particular, x + y + z ≦ 0.2.

[0042] In the formulas a+b+c+d+e=4 and 2a+3b+4c+d+5e=10-y-n+z, respectively, the cations Z, A, B, C, D and E in the lattice and the anions O and N are specifically defined, thereby defining the charge neutrality of the system. For example, charge compensation is covered by the formula 2a+3b+4c+d+5e=10-y-n+z. For example, charge compensation by reducing the amount of O, or by replacing C cations with B cations, or by replacing B cations with A cations, etc. are covered. For example, x=0.01, y=0.02, n=0, a=3; 6+3b+4c=10-0.02; a+b+c=4; b=0.02; c=0.98.

[0043] As will be clear to those skilled in the art, a, b, c, d, e, n, x, y, z are always equal to or greater than zero. If a is defined in combination with a+b+c+d+e=4; and 2a+3b+4c+d+5e=10-y-n+z, then in principle b, c, d, e do not need to be defined any more. However, for completeness, this application defines 0≦b≦4; 0≦c≦4; 0≦d≦4; 0≦e≦4.

[0044] Assume a system such as SrMg2Ga2N4:Eu, where a=2, b=2, c=d=e=y=z=n=0. In such a system, 2+2+0+0+0=4, and 2*2+3*2+0+0+0=10-0-0+0=10. Hence, both equations can be satisfied. Assume that 0.5 O is introduced. For example, substituting 0.5 Ga-N with 0.5 Mg-O (a charge-neutral substitution) results in a system with 0.5 O. This results in SrMg 2.5 Ga 1.5 N 3.5 O 0.5 :Eu. Now, in such a system, 2.5+1.5+0+0+0=4, and 2*2.5+3*1.5+0+0+0=10-0-0.5+0=9.5. So again, both equations are satisfied.

[0045] As mentioned above, in a significant embodiment, d>0 and / or z>0, in particular at least d>0. In particular, the phosphor comprises at least lithium. In yet another embodiment, 2≦a≦3, in particular d=0, e=0 and z=0. In such a case, the phosphor is characterized, inter alia, by a+b+c=4; and 2a+3b+4c=10-yn.

[0046] In another particular embodiment, which may be combined with the former embodiment, e = 0. In yet another particular embodiment, which may be combined with the former embodiment, M is Ca and / or Sr.

[0047] Thus, in certain embodiments, the phosphor has the general formula M(Ca and / or Sr): 1-x-y Mg a Al b S c N 4-n O n :ES x ,RE y (I), where ES is selected from the group consisting of divalent Eu (Europium) or Sm (Samarium) or Yb (Ytterbium), and RE is selected from the group consisting of trivalent Ce (Cerium), Pr (Praseodymium), Nd (Neodymium), Sm (Samarium), Eu (Europium), Gd (Gadolinium), Tb (Terbium), Dy (Dysprosium), Ho (Holmium), Er (Erbium) and Tm (Tulium), with y / x<0.1, in particular <0.01, and n≦0.1, in particular <0.01, in particular <0.001, more in particular <0.0001. Thus, in this embodiment, a phosphor substantially containing samarium and / or europium is described. For example, when divalent Eu is present, x=0.05, e.g., y1 of Pr is 0.001, y2 of Tb is 0.001, and y=yl+y2=0.002. In such an example, y / x=0.04. More specifically, y=0. However, as shown elsewhere, in the application of Eu and Ce, the y / x ratio may be greater than 0.1.

[0048] The condition of 0 x + y ≦ 0.4 indicates that M can be replaced up to a total of 40% of ES and / or RE. The condition "0 < x + y ≦ 0.4" combined with x and y being between 0 and 0.2 represents that at least one of ES and RE exists. It is not necessary for both types to exist. As described above, ES and RE may refer to one or more sub - species, such as ES representing one or more of Sm and Eu individually, and RE representing one or more of Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, and Tm.

[0049] In particular, when europium is applied as a divalent luminescent species or dopant (i.e., Eu 2+ ), the molar ratio (Sm / Eu) between samarium and europium is < 0.1, particularly < 0.01, particularly < 0.001. The same applies when europium combined with ytterbium is applied. When europium is applied as a divalent luminescent species or dopant, the molar ratio (Yb / Eu) between ytterbium and europium is < 0.1, particularly < 0.01, particularly < 0.001. When all three are applied together, the same molar ratio may apply, i.e., ((Sm + Yb) / Eu) may be < 0.1, particularly < 0.01, particularly < 0.001.

[0050] In particular, x is in the range of 0.001 to 0.2 (i.e., 0.001 ≦ x ≦ 0.2), for example 0.002 to 0.2, for example 0.005 to 0.1, particularly 0.005 to 0.08. In particular, for divalent europium in the system described in the present application, the mole % may be in the range of 0.1 to 5% (0.001 ≦ x ≦ 0.05), or 0.2 to 5%, for example 0.5 to 2%. In one embodiment, for other luminescent ions, (although not necessarily) x may be 1% or more (x is equal to or greater than 0.01).

[0051] In certain embodiments, the phosphors are (Sr,Ca)Mg3SiN4:Eu, (Sr,Ca)Mg2Al2N4:Eu, (Sr,Ca)LiAl3N4:Eu, and (Sr,Ca)Li d Mg a Al b N4: Eu, and a, b, d are as defined above.

[0052] Also, as used herein, "(Sr,Ca)" and similar notations with other elements indicate that the M-position is occupied by a cation of Sr and / or Ca (or by the other element, respectively).

[0053] In another specific embodiment, the phosphor is Ba. 0.95 Sr 0.05 Mg2Ga2N4:Eu, BaMg2Ga2N4:Eu, SrMg3SiN4:Eu, SrMg2Al2N4:Eu, SrMg2Ga2N4:Eu, BaMg3SiN4:Eu, CaLiAl3N4:Eu, SrLiAl3N4:Eu, CaLi 0.5 MgAl 2.5 N4: Eu, and SrLi 0.5 MgAl 2.5 N4:Eu. Another (non-limiting) example of such a phosphor is, for example, (Sr 0.8 Ca 0.2 ) 0.995 LiAl 2.91 Mg 0.09 N 3.91 O 0.09 :EU 0.005 ; (Sr 0.9 Ca 0.1 ) 0.905 Na 0.09 LiAl3N 3.91 O 0.09 :EU 0.005 ;(Sr 0.8 C a0.03 Ba 0.17 ) 0.989 LiAl 2.99 Mg 0.01 N4: Ce 0.01 ,EU 0.001 ; Ca 0.995 LiAl 2.995 Mg0.005 N 3.995 O 0.005 :Yb 0.005 (YB(II));Na 0.995 MgAl3N4:Eu 0.005 ; Na 0.985 Ca 0.1 Mg 0.9 Li 0.1 Al3N4:Eu 0.005 ;Sr 0.99 LiMgAlSiN4:Eu 0.01 ;Ca 0.995 LiAl 2.955 Mg 0.045 N 3.96 O 0.04 :Ce 0.005 ;(Sr 0.9 Ca 0.1 ) 0.998 Al 1.999 Mg 2.01 N 3.99 O 0.01 :EU 0.00 2;(Sr 0.9 Ba 0.1 ) 0.998 Al 1.99 Mg 2.01 N 3.99 O 0.01 :EU 0.002 It is.

[0054] In another specific embodiment, the phosphor is selected from the group consisting of (Sr,Ca)Mg3SiN4:Eu and (Sr,Ca)Mg2Al2N4:Eu. In yet another specific embodiment, the phosphor is Ba 0.95 Sr 0.05 In particular, these phosphors, in particular (Sr,Ca)Mg3SiN4:Eu and (Sr,Ca)Mg2Al2N4:Eu, may be phosphors with good emission properties, in particular with regard to the spectral position and distribution of the emission.

[0055] In another particular embodiment, the phosphor, in particular the luminescent material, is (Sr,Ca)LiAl3N4:Eu and (Sr,Ca,Ba)Li d Mg a Al b N4:Eu, where 0≦a≦4; 0≦b≦4; 0≦d≦4; and a+b+d=4 and 2a+3b+d=10. In yet another particular embodiment, the phosphor is (Sr,Ba)Li2Al 2-z S z O 2-z N 2+z :Eu, where 0≦z≦0.1.

[0056] In an embodiment, the luminescent material is selected from the group SrLiAl3N4:Eu. The luminescent material may, for example, have SrLiAl3N4:Eu, with an Eu doping concentration in the range of 0.1-5%, in particular 0.1-2%, for example 0.2-1.2%, relative to Sr.

[0057] In another particular embodiment, the phosphor / luminescent core (luminescent material) is SrLiAl 1.995 S 0.005 O 1.995 N 2.005 :EU 2+ In particular, the Eu doping concentration is in the range of 0.1 to 5% relative to Sr, particularly 0.1 to 2%, 0.2 to 1.5%.

[0058] In phosphors of particular interest, the phosphor satisfies 0≦x≦0.2, y / x<0.1, M is at least Sr, z≦0.1, a≦0.4, 2.5≦b≦3.5, B is at least Al, c≦0.4, 0.5≦d≦1.5, and ES includes at least Eu. In particular, y+z≦0.1. In particular, x+y+z≦0.2. In particular, a is 0 or close to 0. In particular, b is about 3. In particular, c is 0 or close to 0. In particular, d is about 1. In particular, e is 0 or close to 0. In particular, n is 0 or close to 0. In particular, y is 0 or close to 0. Particularly favorable systems in terms of quantum efficiency and hydrolytic stability are those with z+d>0, i.e., one or more of Na, K, Rb, Li and Cu(I) can be used, in particular (Sr,Ca)LiAl3N4:Eu and (Sr,Ca)Li d Mg a Al b In another specific embodiment, the phosphor is CaLiAl3N4:Eu, SrLiAl3N4:Eu, CaLiAl3N4:Eu, SrLiAl3N4:Eu, or SrLiAl3N4:Eu. 0.5 MgAl 2.5 N4: Eu, and SrLi 0.5 MgAl 2.5 Another phosphor of particular interest is (Sr,Ca,Ba)(Li,Cu)(Al,B,Ga)3N4:Eu, which has at least Sr as the M ion, at least Al as the B ion, and at least Li as the D ion.

[0059] In one embodiment, the phosphor (light emitting core) is (M1)Li d Mg a Al b N4: Eu, where 0≦a≦4; 0≦b≦4; 0≦d≦4; M1 includes one or more (selected elements) from the group consisting of Ca, Sr, and Ba, where a+b+d=4 and 2a+3b+d=10; and (M2)Li2Al 2-z Sz O 2-z N 2+z : Eu, where 0≦z≦z 0.1, and M2 includes one or more (selected elements) from the group consisting of Sr and Ba; is selected from the group consisting of:

[0060] Thus, in certain embodiments, the luminescent particles are (SrLiAl 3 N 4 :EU 2+ ) (class). In this application, the term "class" specifically refers to a group of materials having the same crystal structure. The term "class" may also include partial substitution of cations and / or anions. For example, in some of the aforementioned classes, Al-O may be partially substituted with Si-N (or vice versa). SrLiAl3N4:Eu 2+ The class relates in particular to a group of materials having the same crystal structure, in which in particular Sr is partially replaced by divalent Eu, for example by 0.1% or 2%. For example, Sr 0.995 LiAl3N4:Eu 0.005 , and Sr 0.98 LiAl3N4:Eu 0.02 is an element of such a class. Similarly, SrLi2Al 1.995 S 0.005 O 1.995 N 2.005 :EU 2+ The class (see below) is, for example, Sr 0.999 Li2A l1.995 S 0.005 O l.995 N 2.005 :EU 0.001 and Sr 0.985 Li2Al l.995 S 0.005 O l.995 N 2.005 :EU 0.015 If necessary, a portion of the Sr may be replaced with another alkaline earth metal (an element of Group 2 of the periodic table). SrLiAl3N4:Eu 2+ Examples of classes are provided above, however other luminescent materials are possible as well.

[0061] In another embodiment, the luminescent material (or phosphor) is (Sr,Ca)LiAl3N4:Eu, (Sr,Ca,Ba)Li d Mg a Al b N4:Eu, where 0≦a≦4, 0≦b≦4, 0≦d≦4, a+b+d=4 and 2a+3b+d=10; and (Sr,Ba)Li2Al 2-z S z O 2-z N 2+z : Eu, where 0≦z≦0.1; is selected from the group consisting of:

[0062] Thus, the luminescent core may in particular comprise a phosphor. The luminescent core may also comprise a luminescent material as described herein, in particular a phosphor. The method may be applied to provide two or more, in particular a plurality of, luminescent particles with a hybrid coating (in particular covering two or more luminescent cores).

[0063] In another embodiment of the luminescent material, the luminescent core comprises: (i) SrLiAl3N4:Eu 2+ (class), in particular the (Eu) doping concentration is in the range of 0.1 to 5%, in particular 0.1 to 2%, in particular 0.2 to 1.2% relative to Sr, and (ii) SrLiAl 1.995 S 0.005 O 1.995 N 2.005 :EU 2+ (class), in particular, the Eu doping concentration is in the range of 0.1 to 5%, particularly 0.1 to 2%, particularly 0.2 to 1.5 at % relative to Sr, The (phosphor) material is selected from the group consisting of:

[0064] Further, in particular, the third coating layer comprises SiO2, one or more layers of the multilayer comprise one or more of Ta2O5, HfO2, TiO2 and ZrO2, and one or more (other) layers of the multilayer comprise Al2O3, in particular, in the present application, the layer in contact with the main sol-gel coating layer is selected from the group of HfO2, ZrO2, TiO2 and Ta2O5. 、 It is composed of one or more metal oxides.

[0065] Such luminescent particles may have a number-average particle size in the range of 0.1 to 50 μm, for example in the range of 0.5 to 40 μm, in particular in the range of 0.5 to 20 μm. The luminescent core may thus have dimensions, for example up to about 500 μm, such as up to about 100 μm, in particular at larger particle sizes substantially only the individual particles are coated, thus obtaining luminescent core dimensions of the order of 50 μm or less. The invention therefore relates to the coating of particles. The dimensions of the luminescent core may be substantially smaller if nanoparticles or quantum dots are used as the basis for the particulate luminescent material. In such cases the core may be smaller or substantially smaller than about 1 μm (the dimensions of QDs are described below).

[0066] Alternatively or additionally, the luminescent particles, particularly the luminescent cores, have luminescent quantum dots. In one embodiment, the term "quantum dot" or "luminescent quantum dot" can also refer to a combination of different types of quantum dots, i.e., a combination of quantum dots with different spectral characteristics. QDs are also referred to as "wavelength conversion nanoparticles" or "luminescent nanoparticles". The term "quantum dot" particularly refers to quantum dots that emit light in one or more of UV, visible and IR (upon excitation with suitable radiation, such as UV radiation). Quantum dots or luminescent nanoparticles, referred to herein as wavelength converting nanoparticles, may comprise, for example, II-VI compound semiconductor quantum dots selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe (core-shell quantum dots, the core being selected from the group consisting of). In another embodiment, the luminescent nanoparticles may be III-V compound semiconductor quantum dots selected from the group consisting of, for example, GaN, GaP, GaAs, AlN, AlP, AlAs, InN, InP, InGaP, InAs, GaNP, GaNAs, GaPAs, AlNP, AlNAs, AlPAs, InNP, InNAs, InPAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaINAs, GaInPAs, InAlNP, InAlNAs, and InAlPAs (core-shell quantum dots having a core selected from the group consisting of).

[0067] In yet another embodiment, the luminescent nanoparticles may be I-III-VI2 chalcopyrite-type semiconductor quantum dots, for example, selected from the group consisting of CuInS2, CuInSe2, CuGaS2, CuGaSe2, AgInS2, AgInSe2, AgGaS2, and AgGaSe2 (core-shell quantum dots having a core selected from the group consisting of). In yet another embodiment, the luminescent nanoparticles may be IV-VI semiconductor quantum dots (core-shell quantum dots having a core selected from the group consisting of), for example, (core-shell quantum dots having a core selected from the group consisting of LiAsSe2, NaAsSe2, and KAsSe2 (core-shell quantum dots having a core selected from the group consisting of). In yet another embodiment, the luminescent nanoparticles may be core-shell quantum dots having a core selected from the group consisting of (IV-VI compound semiconductor nanocrystals), for example, SbTe. In a particular embodiment, the luminescent nanoparticles may be core-shell quantum dots having a core selected from the group consisting of InP, CuInS2, CuInSe2, CdTe, CdSe, CdSeTe, AgInS2, and AgInSe2 (core-shell quantum dots having a core selected from the group consisting of). In yet another embodiment, the luminescent nanoparticles may be one of the group of (core-shell quantum dots with a core selected from the group consisting of) II-VI, III-V, I-III-V and IV-VI compound semiconductor nanocrystals, selected from the aforementioned materials, with internal dopants, such as ZnSe:Mn, ZnS:Mn. The dopant elements may be selected from Mn, Ag, Zn, Eu, S, P, Cu, Ce, Tb, Au, Pb, Tb, Sb, Sn and Tl. Here, the luminescent material of the luminescent nanoparticle system may comprise different types of QDs, such as CdSe and ZnSe:Mn. The luminescent core may comprise one or more, in particular more (types of) luminescent nanoparticles (same or different).

[0068] The use of II-VI quantum dots appears to be particularly advantageous. Thus, in one embodiment, the semiconductor-based light-emitting quantum dots are, in particular, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnSe, HgZnSe, Hg The II-VI quantum dots are selected from the group consisting of ZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe (core-shell quantum dots having a core selected from the group consisting of), and in particular are selected from the group consisting of CdS, CdSe, CdSe / CdS, and CdSe / CdS / ZnS.

[0069] In one embodiment, the wavelength-converting nanoparticles have an average particle size in the range of about 1 to about 1000 nanometers (nm), preferably in the range of about 1 to about 100 nm. In an embodiment, the nanoparticles have an average particle size in the range of about 1 to about 20 nm. In one embodiment, the nanoparticles have an average particle size in the range of about 1 to about 10 nm. The luminescent nanoparticles (uncoated) may have a dimension in the range of about 2 to 50 nm, for example 2 to 20 nm, particularly 2 to 10 nm, more particularly 2 to 5 nm, and in particular at least 90% of the nanoparticles have a dimension in the indicated range, respectively (i.e. at least 90% of the nanoparticles have a dimension in the range of 2 to 50 nm, or in particular at least 90% of the nanoparticles have a dimension in the range of 2 to 5 nm). The term "dimension" particularly relates to one or more of length, width, and diameter, depending on the shape of the nanoparticle. The dots are typically composed of binary alloys such as cadmium selenide, cadmium sulfide, indium arsenide, and indium phosphide. However, the dots may be composed of ternary alloys such as cadmium selenide sulfide. These quantum dots may have a diameter of 10-50 atoms and contain 100-100,000 atoms within the quantum dot volume. This corresponds to about 2 to 10 nanometers. For example, spherical particles such as CdSe, InP, or CuInSe2 with a diameter of about 3 nm may be provided. The luminescent nanoparticles (uncoated) may have shapes such as spheres, cubes, rods, wires, disks, multipods, etc., with a size of less than 10 nm in one dimension. For example, nanorods of CdSe with a length of 20 nm and a diameter of 4 nm may be provided. Thus, in one embodiment, the semiconductor-based luminescent quantum dots comprise core-shell quantum dots. In another embodiment, the semiconductor-based luminescent quantum dots comprise dot-in-rod nanoparticles. A combination of different types of particles may be applied. In this application, the term "different types" may relate to different geometric shapes and different types of semiconductor luminescent materials. Thus, a combination of two or more (as mentioned above) quantum dots or luminescent nanoparticles may be applied.

[0070] In some embodiments, the nanoparticles include semiconductor nanocrystals having a core comprising a first semiconductor material and a shell comprising a second semiconductor material, the shell being disposed on at least a portion of a surface of the core. Semiconductor nanocrystals comprising a core and a shell are also referred to as "core / shell" semiconductor nanocrystals. Any of the aforementioned materials may be used specifically as the core. Thus, the term "core-shell quantum dots having a core selected from the group consisting of" applies to some of the aforementioned lists of quantum dot materials. The term "core-shell" may also refer to gradient alloy shells, or "core-shell-shell" including dot-in-rods, and the like.

[0071] For example, a semiconductor nanocrystal may have a core having the general formula MX, where M is cadmium, zinc, magnesium, mercury, aluminum, gallium, indium, thallium, or mixtures thereof, and X is oxygen, sulfur, selenium, tellurium, nitrogen, phosphorus, arsenic, antimony, or mixtures thereof. Examples of materials suitable for use as semiconductor nanocrystal cores include, but are not limited to, ZnO, ZnS, ZnSe, ZnTe, CdO, CdS, CdSe, CdTe, MgS, MgSe, GaAs, GaN, GaP, GaSe, GaSb, HgO, HgS, HgSe, HgTe, InAs, InN, InP, InGaP, InSb, AlAs, AIN, AlP, AlSb, TIN, TIP, TlAs, TlSb, PbO, PbS, PbSe, PbTe, Ge, Si, alloys comprising any of the foregoing, and / or mixtures comprising any of the foregoing, including ternary, quaternary mixtures or alloys.

[0072] The shell can be a semiconductor material having a composition the same as or different from that of the core. The shell comprises an overcoat of semiconductor material on a surface of the core, the semiconductor nanocrystals comprising Group IV elements, II-VI compounds, II-V compounds, III-VI compounds, III-V compounds, IV-VI compounds, I-III-VI compounds, II-IV-VI compounds, II-IV-V compounds, alloys comprising any of the foregoing, and / or mixtures comprising any of the foregoing, including ternary and quaternary mixtures or alloys. Examples include, but are not limited to, ZnO, ZnS, ZnSe, ZnTe, CdO, CdS, CdSe, CdTe, MgS, MgSe, GaAs, GaN, GaP, GaSe, GaSb, HgO, HgS, HgSe, HgTe, InAs, InN, InP, InGaP, InSb, AlAs, AlN, AlP, AlSb, TIN, TIP, TlAs, TlSb, PbO, PbS, PbSe, PbTe, Ge, Si, alloys containing any of the foregoing, and / or mixtures containing any of the foregoing. For example, an overcoat of ZnS, ZnSe, or CdS can be grown on semiconductor nanocrystals of CdSe or CdTe. Overcoat processes are described, for example, in U.S. Pat. No. 6,322,901. By adjusting the temperature of the reaction mixture during overcoating and monitoring the absorption spectrum of the core, an overcoat material with high radiative quantum efficiency and narrow size distribution can be obtained. The overcoat may have one or more layers. The overcoat has at least one semiconductor material, which may be the same or different in composition from the core. The overcoat preferably has a thickness of about 1 to about 10 monolayers. Also, the overcoat may have a thickness of 10 or more monolayers. In some embodiments, the core may contain two or more overcoats.

[0073] In one embodiment, the surrounding "shell" material may have a bandgap larger than that of the core material. In some other embodiments, the surrounding shell material may have a bandgap smaller than that of the core material. In one embodiment, the shell may be selected to have atomic spacing close to that of the "core" substrate. In certain other embodiments, the shell material and the core material may have the same crystal structure.

[0074] Examples of semiconductor nanocrystal (core)shell materials include, but are not limited to, red (e.g., (CdSe)ZnS (core)shell), green (e.g., (CdZnSe)CdZnS (core)shell), and blue (e.g., (CdS)CdZnS (core)shell) (see further above for examples of certain semiconductor-based wavelength converting nanoparticles).

[0075] Thus, in one embodiment, the luminescent particle or luminescent core comprises a luminescent material selected from the group consisting of luminescent quantum dots, including one or more core materials selected from the group consisting of CdS, CdSe, ZnS, and ZnSe. Thus, in one embodiment, the luminescent particle or luminescent core may be selected from the group of luminescent nanoparticles, such as quantum dots or quantum rods of composition MX (M=Cd, Zn, X=Se, S). Such particles may have a number average particle size (i.e., especially length / width / height, diameter) in the range of 1-50 nm.

[0076] As mentioned above, the luminescent particles have a main ALD coating layer configured, inter alia, on the primer layer. In an embodiment, the luminescent particles may further have another ALD coating layer configured (on) the main sol-gel coating layer. The main ALD coating layer may be deposited by application of a main atomic layer deposition process ("main ALD process"). The other ALD coating layer may be deposited by application of another atomic layer deposition process ("other ALD process"). The main atomic layer deposition process and the (any) other atomic layer deposition process are both atomic layer deposition processes ("ALD processes"). It is understood that these processes may have the same ALD process. However, for example, the conditions of the main ALD process may be different from the conditions of the other ALD process. For example, the metal oxide precursor used in the main ALD process may be different from that used in the other ALD process. The deposition time, temperature, etc. may be different. However, in particular, the metal oxide precursor that may be applied in the other ALD process may be the metal oxide precursor described for the (main) ALD process (and vice versa).

[0077] Thus, the main ALD coating layer and any further ALD coating layers may be formed by an atomic layer deposition type process. In such a process, a polymer network is formed by reaction of a metal oxide precursor with an oxygen source such as moisture and / or ozone in the gas phase. The ALD reaction is "separated" into (at least) two parts. In the first stage, a metal (oxide) precursor is fed into the (n ALD) reactor, where it adsorbs and / or reacts with reactive groups on the particle surface, and substantially all unreacted or non-adsorbed precursor molecules are removed by purging the reactor. In the second stage, an oxygen source is fed into the reactor, where it reacts with the metal source on the particle surface, and then the reactor is purged to remove substantially all remaining oxygen source molecules and hydrolysis products formed by condensation reactions. The two stages result in the formation of an atomic layer (or monolayer) due to the self-limiting nature of the surface reaction. These atomic layer reaction steps may be repeated multiple times to form the final ALD coating. Additionally, ALD processes allow the deposition of layers of different compositions by sequentially feeding different metal oxide precursors into the reactor to form multi-component layers or nanolaminates with tailored chemical, mechanical, and optical properties (see below).

[0078] The term "metal oxide precursor" particularly refers to a precursor of a metal oxide. The precursor itself may not be a metal oxide, but may for example comprise a metal-organic molecule. Thus, in particular, metal (oxide) precursors for ALD may typically comprise metal halides, alkoxides, amides, and other metal (organic) compounds. The term "metal oxide precursor" may relate to one or more different metal oxide precursors, in particular two or more different metal oxides.

[0079] The step-by-step nature of the ALD process allows for easy deposition of layers of defined thickness. ALD processes also allow for deposition of layers of different compositions by sequentially feeding different metal oxide precursors into the reactor to form multi-component layers or nanolaminates. Thus, in certain embodiments, the main ALD coating layer (and / or the additional ALD coating layers) have a multilayer (or nanolaminate) (see also below).

[0080] In the ALD process, in particular a fluidized bed reactor may be applied.

[0081] Thus, in a particular embodiment, the main ALD coating layer is provided by application of a (main) atomic layer deposition process. Also, in an embodiment, the further ALD coating layer is (also) provided by application of a (further) ALD process. In an embodiment, a stationary powder bed is used for the ALD coating of the primer layer and / or the ALD coating of the main sol-gel coating. However, a fluidized bed (for one or more ALD processes) may also be applied. Other types of reactors may also be applied. As mentioned above, the primer layer may in particular act as a nucleation or seed layer for the main ALD coating layer, thereby facilitating the deposition of the main ALD coating layer. In particular, reactive groups on the particle surface may be provided by the primer layer (and the main sol-gel coating layer).

[0082] For example, silanol groups on the surface of a sol-gel coating layer (assuming a primary and / or main silica sol-gel coating layer) act as reaction sites during the ALD of the initial layer. In one embodiment, alumina is deposited using Al(CH3)3 (TMA) as the metal oxide precursor and water (which is subsequently exposed) as the oxygen source. In the first reaction step, TMA reacts with the surface silanol groups of the silica sol-gel coating layer as follows: ≡Si-OH+Al(CH3)3→≡Si-O-Al(CH3)2+CH4 Then, in a second reaction step, water reacts with the metal oxide precursor via hydrolysis and condensation reactions: ≡Si-O-Al(CH3)2+2H2O→≡Si-O-Al(OH)2+2CH4 2≡Si-O-Al(OH)2→≡Si-O-Al(OH)-O-Al(OH)-O-Si≡+H2O Furthermore, particle agglomeration may be substantially prevented by applying a primer sol-gel layer (and a main sol-gel coating layer) with a structured nanoporous surface, such as a silica sol-gel coating layer (see below).

[0083] The ALD process can be easily scaled up, and little loss of powder or particles is observed during ALD coating. Commercially available ALD reactors for powder coating are available, for example, from Picosun Oy, along with a cartridge sample holder (POCA™). Systems that can be used for the ALD process are described, for example, in International Publication No. WO 2013 / 171360 A1. However, other systems may also be applied.

[0084] The following table lists a (non-limiting) number of materials suitable for ALD coating layers:

[0085] [Table 1] Alternatively or additionally, niobium oxide (particularly Nb2O5) or yttrium oxide (Y2O3) may be applied. The metal precursors are, for example, (tert-butylimido)-tris(diethylamino)-niobium, NbF5 or NbCl5 and tris(ethylcyclopentadienyl)yttrium, respectively. In another embodiment, zinc oxide (ZnO) may be applied. For example, the metal precursors that may be applied are diethylzinc (DEZ), Zn(C2H5)2, and dimethylzinc (DMZ)Zn(CH3)2. However, other materials may also be applied. Thus, in the atomic layer deposition process, the metal oxide precursor may be selected from the group of metal oxide precursors, in particular of metals including Al, Zn, Hf, Ta, Zr, Ti, and Sn (and optionally Si). Alternatively or additionally, metal precursors of one or more metals including Ga, Ge, V, and Nb may be applied. More particularly, two or more alternating layers of these precursors are deposited, with at least one precursor being an Al metal oxide precursor and another precursor being selected from the group consisting of Hf metal oxide precursor, Zn metal oxide precursor, Ta metal oxide precursor, Zr metal oxide precursor, Ti metal oxide precursor, and Sn metal oxide precursor, in particular selected from the group consisting of Hf metal oxide precursor, Ta metal oxide precursor, Ti metal oxide precursor, and Zr metal oxide precursor, for example selected from the group consisting of Hf metal oxide precursor, Ta metal oxide precursor, and Zr metal oxide precursor, in particular selected from Ta metal oxide precursor. In particular, Hf, Zr, and Ta appear to provide a relatively light-transmitting layer, while Ti may, for example, provide a relatively low light-transmitting layer. By using TiCl4 as the metal oxide precursor (for the TiO2 layer), a cost-effective layer may be provided. For example, processing with Ta, Hf, and Zr appears to be relatively easier than with Si. The terms "oxide precursor", "metal oxide precursor", or "metal (oxide) precursor" may also refer to a combination of two or more chemically distinct precursors. These precursors form oxides, particularly upon reaction with an oxygen source (and are therefore referred to as metal oxide precursors).In one embodiment, the metal oxide precursors may be selected independently of each other for successive ALD cycles. For example, in one embodiment, ZnO and Al2O3 layers are deposited alternately to obtain an AZO layer (Al2O3:ZnO, or "aluminum-doped zinc oxide layer"). The AZO layer may be a conductive layer and may be deposited, for example, using triethylaluminum, diethylzinc, and water as oxygen sources. In another embodiment, a (different) metal oxide is deposited in multiple successive cycles (optionally, another metal oxide may be deposited in succession (if necessary)).

[0086] Furthermore, the phrases "metal oxide precursors of metals including Al, Zn, Hf, Ta, Zr, Ti, and Sn" and "in the atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals including Al, Zn, Hf, Ta, Zr, Ti, and Sn" specifically refer to metal oxide precursors of metals selected from the group consisting of a given metal (in this respect, Al, Zn, Hf, Ta, Zr, Ti, Sn). Furthermore, in one embodiment, one or more metal oxide precursors are selected. For example, with respect to the above list, the metal oxide precursor "selected from the group of metal oxide precursors of metals including Al, Zn, Hf, Ta, Zr, Ti, and Sn" may include any combination of metal oxide precursors of two or more metals selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, and Sn. In one embodiment, for example, the metal oxide precursor includes a combination of TaCl5 and HAl(CH3)2. In another embodiment, the metal oxide precursor includes only Al(CH3)3.

[0087] Thus, in one embodiment, in the principal atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si). In particular, in another embodiment, in the principal atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals including Al, Hf, Ta, Zr, and Ti (in particular, metal oxide precursors of metals selected from the group consisting of Al, Hf, Ta, Zr, and Ti). In another embodiment, in the principal atomic layer deposition process, a metal oxide precursor selected from the group consisting of Al(CH3)3, HAl(CH3)2, Hf(N(CH3)2)4, Hf(N(CH2)(CH3)2)4, Hf[N(CH3)(CH2CH3)]4, TaCl5, Ta(N(CH3)2)5, Ta{[N(CH3)(CH2CH3)]3N(C(CH3)3)}, ZrCl4, Zr(N(CH3)2)4, TiCl4, Ti(OCH3)4, and Ti(OCH2CH3)4, and an oxygen source selected from the group consisting of H2O and O3, is applied. Alternatively or additionally, in the (principal) atomic layer deposition process, the metal oxide precursor is selected from the group consisting of Zn(C2H5)2 and Zn(CH3)2. In yet another embodiment, alternatively or additionally, in the (main) atomic layer deposition process, the metal precursor is selected from the group consisting of (tert-butylimido)-tris(diethylamino)-niobium, NbF5, NbCl5, and tris(ethylcyclopentadienyl)yttrium.

[0088] The metal oxide precursor in the alternative atomic layer deposition process may in particular be independently selected from the metal oxide precursor in the main atomic layer deposition process, in particular (also) from the group of metal oxide precursors of metals selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si). In an embodiment, (at least one of) the metal oxide precursor in the alternative atomic layer deposition process is a Si metal oxide precursor. In particular, in another embodiment, in the alternative atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Hf, Ta, Zr, and Ti. In one embodiment, in the alternative atomic layer deposition process, the metal oxide precursor is selected from the group consisting of Al(CH3)3, HAl(CH3)2, Hf(N(CH3)2)4, Hf(N(CH2CH3)2)4, Hf[N(CH3)(CH2CH3)]4, TaCl5, Ta(N(CH3)2)5, Ta{[N(CH3)(CH2CH3)]3N(C(CH3)3)}, ZrCl4, Zr(N(CH3)2)4, TiCl4, Ti(OCH3)4, and Ti(OCH2CH3)4, and an oxygen source selected from the group consisting of H2O and O3 is applied (independently from the main ALD process). Additionally or alternatively, in the alternative atomic layer deposition process, the metal oxide precursor is selected from the group consisting of Zn(C2H5)2 and Zn(CH3)2. In yet another embodiment, additionally or alternatively, in another atomic layer deposition process, the metal precursor is selected from the group consisting of (tert-butylimido)-tris(diethylamino)-niobium, NbF5, NbCl5, and tris(ethylcyclopentadienyl)yttrium.

[0089] In particular, in one embodiment, in the principal atomic layer deposition process and / or in the alternative atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, Si, Sn, Nb, Y, Ga, and V.

[0090] Deposition temperatures in the range of 200-350° C. have been found to be most suitable for the ALD of alumina on the primer layer (and main sol-gel coating layer), with temperatures preferably in the range of 250-300° C. Similar temperatures may be applied for the ALD of other metal oxide precursors for the ALD layers.

[0091] In a particular embodiment, the main ALD coating layer has a multilayer of at least three layers with different chemical compositions, one or more of the layers comprising an oxide of Si (SiO2). In particular, such a SiO2 layer is sandwiched between other layers of the multilayer. Thus, in particular, the (ALD) layer (of the multilayer of the main ALD coating layer) in contact with the main sol-gel layer and each (ALD) layer in contact with the primer layer does not consist of SiO2. Furthermore, in an embodiment, another ALD coating layer in contact with the main sol-gel coating layer may comprise SiO2. Thus, in an embodiment, a metal oxide precursor of Si is selected in the (main and / or another) atomic layer deposition process.

[0092] In particular, the main ALD alumina (or other metal oxide) layer has a thickness of 3 to 250 nm, in particular a thickness of 5 to 250 nm, such as a thickness of 5 to 100 nm, in particular a thickness of 5 to 50 nm, for example a thickness of 10 to 50 nm, in particular a thickness of 20 to 50 nm.

[0093] The water vapor permeation barrier properties of the alumina ALD layer can be further improved by depositing at least one additional layer of a different oxide material, such as ZrO2, TiO2, Y2O3, Nb2O5, HfO2, Ta2O5. In particular, the thickness of the additional material layer is in the range of 1-40 nm, more preferably in the range of 1-10 nm. More particularly, a nanolaminate laminate stack of alternating layers of Al2O3 and a second oxide material from the group ZrO2, TiO2, Y2O3, Nb2O5, HfO2, SnO2, Ta2O5 is preferred. A suitable nanolaminate stack can be, for example, 20×(1 nm Al2O3 (10 ALD cycles)+1 nm ZrO2 (11 ALD cycles)) deposited at 250° C., forming a 40 nm thick second coating of nanolaminate on the primer layer (and / or the main sol-gel coating layer).

[0094] In one embodiment, the present invention provides, among other things, a method, where the main ALD coating layer has a multi-layer with layers of different chemical composition, and in the atomic layer deposition process, the metal oxide precursor is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Zn, Hf, Ta, Zr, Ti, Sn, Y, Ga, Ge, V and Nb (and optionally Si), in particular, the metal oxide precursor is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Hf, Ta, Zr and Ti. Also, combinations of two or more such precursors may be used, for example, multi-layers including alumina-mixed oxide of zirconium and hafnium-alumina, etc. In a particular embodiment, in the main atomic layer deposition process, the metal oxide precursors of two or more layers are selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Hf, Ta, Zr and Ti.

[0095] Thus, in one embodiment, the main ALD coating layer may have a multilayer having (n) layers with different chemical compositions, the multilayer having one or more layers comprising an oxide of one or more of Al, Zn, Hf, Ta, Zr, Ti, Sn, Y, Ga, Ge, V, and Nb (and optionally Si), in particular the multilayer having one or more layers comprising an oxide of one or more of Al, Hf, Ta, Zr, and Ti. One or more layers of such a multilayer may comprise mixed oxides as described above.

[0096] In another particular embodiment, the method of the invention comprises the step of providing n layers successively (on a primer layer by application of a principal atomic layer deposition process), in particular each layer having a layer coating thickness (d21) in the range of 1 to 50 nm, in particular 1 to 20 nm, for example 1 to 15 nm. In one embodiment, the layer coating thickness may be at least 2 nm, for example at least 5 nm, for example in the range of 5 to 40 nm, in particular 5 to 25 nm. The number of layers n is in particular at least 2, for example at least 3 or at least 4. In one embodiment, n may be greater than 10. However, n may in particular be less than or equal to 10, for example less than or equal to 5. In one embodiment, 2≦n≦10, or in particular 2≦n≦5. It is understood that the individual layers may be provided by one or more ALD cycles. Furthermore, in particular adjacent (contacting) layers have different chemical compositions. In another embodiment, the layer or layers comprise one or more metal oxides selected from the group HfO2, ZrO2, TiO2, Ta2O5, in particular the (other) layer or layers comprise Al2O3. It may also be advantageous for the layer in contact with the main sol-gel coating layer to be composed of HfO2 and / or ZrO2 and / or TiO2 and / or Ta2O5. Thus, in another embodiment, the layer in contact with the main sol-gel coating layer is composed of one or more metal oxides selected from the group HfO2, ZrO2, TiO2, Ta2O5.

[0097] Thus, in certain embodiments, the method comprises the step of successively providing n (ALD) layers on the primer layer by application of a (multi-layer providing) atomic layer deposition process, each layer having a coating layer thickness (d21) in the range of 1 to 50 nm, particularly in the range of 1 to 20 nm, for example in the range of 1 to 15 nm, where 2 < n ≤ 50, particularly 2 < n ≤ 20, for example 2 ≤ n ≤ 10, particularly 2 ≤ n ≤ 5, and one or more of the layers have one or more metal oxides selected from the group of HfO2, ZrO2, TiO2, Ta2O5, one or more of the layers have Al2O3, and the layer in contact with the main sol-gel coating layer is composed of one or more metal oxides selected from the group of HfO2, ZrO2, TiO2, Ta2O5.

[0098] In particular, the method is applied such that an (n-layer ALD) multi-layer coating (particularly the main ALD coating layer) is obtained that comprises at least two (ALD) layers ("AB"), more particularly at least three layers (e.g., "ABA"), and even more particularly at least four layers. Even more particularly, a stack is provided that comprises two or more stacks of a subset of at least two (ALD) layers ("AB") (e.g., (AB) n ) where n is two or more, for example 2 to 20, for example 2 to 10.

[0099] In particular, at least one of the layers of the multi-layer comprises an oxide of Al (optionally, for example, in combination with another oxide of Si or other metal oxides described herein), and at least one of the layers of the multi-layer comprises one or more of the oxides of Hf, Zn, Ta, Zr, Ti, Y, Ge, Ge, V, Sn, and Nb. Such layers may optionally have Al, Zn, Hf, Ta, Zr, Ti, Sn, (Si), Y, Ga, Ge, Ge, V, and Nb, where Al is present in the layer together with one or more of the other indicated elements if the other layers of the multi-layer each comprise an oxide of alumina. The terms "ALD multi-layer" or "multi-layer" as used above particularly denote layers having different chemical compositions. The phrase "layers having different chemical compositions" means, as in the case of "ABC", or (AB)n (where n≧1), indicates that there are at least two layers with different chemical compositions.

[0100] (AB) n Specific examples include multilayers in which A is an oxide of Al and B is selected from one or more of the oxides of Al, Zn, Hf, Ta, Zr, Ti, Sn, Y, Ga, Ge, V, and Nb, and Al (and / or optionally Si) is present in a layer together with one or more of the other indicated elements, and in which the other layers of the multilayer each have an oxide of alumina, in particular B is selected from one or more of the oxides of Hf, Zn, Ta, Zr, Ti, Y, Ge, Ge, V, and Nb, in particular B is selected from one or more of the oxides of Hf, Ta, Zr, and Ti, in particular B is selected from one or more of the oxides of Hf, Ta, Zr. In one embodiment, B may further comprise an oxide of Si (optionally combined with one or more of the oxides of Al, Zn, Hf, Ta, Zr, Ti, Sn, Y, Ga, Ge, V, and Nb). In particular, if the SiO2 layer is deposited by ALD, the SiO2 (ALD) layer is deposited such that it is not in direct contact with the primary sol-gel layer. For example, the A (or B) layer of the multilayer may be a SiO2 layer, and the B (or A) layer in contact with the primary sol-gel layer may be an (ALD) layer having a different chemical composition.

[0101] Thus, in particular, the main ALD multilayer is provided on a primer layer. A main sol-gel layer is provided in particular on the main ALD multilayer. Furthermore, as mentioned above, one or more further layers may be optionally provided on top of the main sol-gel layer, in particular, another ALD layer may be provided on top of the main sol-gel layer. The further ALD layer may comprise an ALD multilayer, for example, an ALD multilayer as described herein with respect to the main ALD multilayer.

[0102] In another particular embodiment, the method comprises (iv) providing another ALD coating layer on the light emitting core with the main sol-gel coating by applying another atomic layer deposition process. In particular, this provides another ALD coated light emitting particle. In the another atomic layer deposition process, in particular the metal oxide precursor is selected from the group of metal oxide precursors including Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V (and optionally Si), in particular Al, Hf, Ta, Zr, Ti. In one embodiment, the another ALD coating layer has a another ALD coating layer thickness (d4) in the range of 2-50 nm, in particular 10-50 nm, for example 10-20 nm. The another ALD coating layer in particular has a chemical composition different from the chemical composition of the main sol-gel coating layer.

[0103] In another embodiment, the further ALD coating layer comprises (is provided to comprise) a further multilayer having two or more (further sub)layers with (optionally) different chemical compositions, one or more layers having a metal oxide selected from the group Al2O3, TiO2, ZrO2, HfO2, SnO2, ZnO and Ta2O5, and two or more layers having a chemical composition different from the chemical composition of the main sol-gel coating layer. In a particular embodiment, in the further atomic layer deposition process, the metal oxide precursor of two or more (further sub)layers (of the further multilayer) is selected from the group of metal oxide precursors of metals selected from the group consisting of Al, Hf, Ta, Zr, and Ti. The metal oxide precursor of two or more (further sub)layers (of the further multilayer) is selected from the group of metal oxide precursors including, in particular, Al, Hf, Ta, Zr, Ti.

[0104] Thus, in a particular embodiment, the main ALD coating layer comprises a multilayer having a stack of layers, where adjacent layers have different chemical compositions. In particular, the layers of the multilayer each independently have a thickness in the range of 1-40 nm, in particular in the range of 1-10 nm. More particularly, the multilayer comprises one or more alumina layers and one or more metal oxide layers, where the metals are selected from the group of Hf, Ta, Zr and Ti.

[0105] Thus, in a particular embodiment of the atomic layer deposition process, a metal oxide precursor selected from the group consisting of Al(CH3)3, HAl(CH3)2, Hf(N(CH3)2)4, Hf(N(CH2CH3)2)4, Hf[N(CH3)(CH2CH3)]4, TaCl5, Ta(N(CH3)2)5, Ta{[N(CH3)(CH2CH3)]3N(C(CH3)3)}, ZrCl4, Zr(N(CH3)2)4, TiCl4, Ti(OCH3)4, and Ti(OCH2CH3)4, and an oxygen source selected from the group consisting of H2O and O3, is applied. As mentioned above, two or more different metal oxide precursors and / or two or more different oxygen sources may be applied.

[0106] Furthermore, in one embodiment of the method in the main atomic layer deposition process and / or another atomic layer deposition process, in particular in the main atomic layer deposition process, a multilayer is provided with layers having different chemical compositions, one or more of which may comprise tantalum oxide (particularly Ta2O5). Thus, in an embodiment, the present invention provides a luminescent material, in which the main ALD coating layer comprises a multilayer with layers having different chemical compositions, one or more of which may comprise Ta2O5 in particular. Furthermore, in an embodiment of the method, in a (main) atomic layer deposition process, a multilayer is provided with layers having different chemical compositions, one or more of which may comprise tantalum oxide (particularly Ta2O5), hafnium oxide, titanium oxide, and zirconium oxide in particular. Thus, the present invention also provides a luminescent material, in particular a luminescent particle, in which the main ALD coating layer comprises a multilayer with layers having different chemical compositions, one or more of which may comprise tantalum oxide, hafnium oxide, titanium oxide, and zirconium oxide in particular. Also for example, the multilayer stack may have, for example, a stack of alternating layers, such as alumina alternating with one or more of tantalum oxide (particularly Ta2O5), hafnium oxide, titanium oxide, and zirconium oxide, such as a stack having alumina-tantalum oxide-alumina-hafnia-alumina-tantalum oxide, or alumina-titanium oxide-alumina, etc.

[0107] Furthermore, if an ALD coating is first deposited on a core without a primer layer, the ALD layer appears to be less uniform than desired. In such an embodiment, in order to obtain a good ALD layer directly on the core surface, the thickness of the ALD layer would in principle have to be thicker than necessary, which could lead to an unwanted (albeit small, in some cases) decrease in permeability. Furthermore, after providing a primer layer to the core, the ALD coating appears to coat the core easily (even if not completely conformal).

[0108] As mentioned above, the main sol-gel layer usually has an average thickness in the range of 50-700 nm, e.g. 50-600 nm, in particular 75-500 nm, e.g. 100-500 nm, and is formed by a sol-gel type process. In such a method, an inorganic network is formed from a homogeneous solution of precursors, which are then hydrolyzed to form a sol (colloidal suspension) and condensed to form a gel (crosslinked solid network), which is chemically bonded to the powder surface. Preferably, the (main) sol-gel coating layer material is silica, and the sol-gel deposition method corresponds to the so-called Stober reaction, as described in Stober, W., A. Fink et al., "Controlled growth of monodisperse silica spheres in the micron size range", Journal of Colloid and Interface Science 26(1): 62-69. For this, luminescent particles (coated or uncoated) are dispersed in an alcohol, such as an aliphatic alcohol R-OH, e.g. methanol CH3OH, ethanol C2H5OH, or isopropanol C3H7OH. Ammonia (NH3 solution in water) and silicon alkoxide precursor are then added. The silicon alkoxide precursor dissolves in the alcohol + ammonia mixture and hydrolysis is initiated. The hydrolysis reaction forms a conformal silica coating on the particle surface (coated or uncoated), while the sol species with reactive groups (e.g. amine or silanol groups) on the particle surface are dissolved, and then a seed growth process is carried out, consisting of the steps of hydrolysis, nucleation, and condensation reactions.

[0109] The term "particle surface (coated or uncoated)" in relation to a sol-gel coating process particularly relates to the surface of the particle (light emitting core) in relation to a primary sol-gel coating process and / or the surface of a washed layer (particularly an oxide-containing layer) on the particle (light emitting core). Furthermore, the term particularly relates to the surface of the main ALD coating in relation to a main sol-gel coating process.

[0110] The silicon alkoxide precursor is in particular

[0111] [ka] wherein the compound is selected from the group of compounds formed by a) R1, R2, and R3 are hydrolyzable alkoxy groups, and R4 is selected from the group consisting of C1-C6 linear alkyl groups, hydrolyzable alkoxy groups, and phenyl groups; or b) R1, R2, and R3 are individually selected from -OCH3 and -OC2H5, and R4 is selected from -CH3, -C2H5, -OCH3, -OC2H5, and a phenyl group.

[0112] If desired, the silicone-based polymer is obtained from a material from the following group:

[0113] [ka] Thus, in an embodiment of the method, a silicon alkoxide precursor is used in the main sol-gel coating process, the silicon alkoxide precursor being, in particular,

[0114] [ka] wherein the compound is selected from the group of compounds consisting of a) R1, R2, and R3 are hydrolyzable alkoxy groups, and R4 is selected from the group consisting of C1-C6 linear alkyl groups, hydrolyzable alkoxy groups, and phenyl groups; or b) R1, R2, and R3 are individually selected from -OCH3 and -OC2H5, and R4 is selected from -CH3, -C2H5, -OCH3, -OC2H5, and a phenyl group.

[0115] In another embodiment of the method, a silicon alkoxide precursor is used in the primary sol-gel coating process, the silicon alkoxide precursor being

[0116] [ka] is selected from the group consisting of:

[0117] In another embodiment of the method, a silicon alkoxide precursor is used in the primary sol-gel coating process, and in particular the silicon alkoxide precursor may be a silicon alkoxide precursor as described herein with respect to the primary sol-gel coating process. The silicon alkoxide precursor in the primary sol-gel coating process may be independently selected from the silicon alkoxide precursor in the primary sol-gel coating process.

[0118] In particular, the silicon alkoxide precursor (in the main and / or primary sol-gel coating process) is selected from the group of Si(OCH3)4 or Si(OC2H5)4, in particular Si(OC2H5)4 is used as silicon alkoxide precursor. Similar precursors based on other metals, such as Al, may also be used.

[0119] A typical sol-gel coating process may have the following steps: (a) Particles or powders, especially luminescent cores (with oxide-containing layers and / or main ALD coating layers, if necessary), are suspended in an alcohol-aqueous ammonia mixed solution and stirred or sonicated. Alternatively, to improve particle dispersion, the particles (cores / powder) may be mixed with alcohol first and a small amount of silicon (or other metal) alkoxide is added before the ammonia solution is added. (b) Under stirring of the suspension, silicon (or other metal) alkoxide precursor is added. Typical concentrations of silicon (or other metal) alkoxide, ammonia, and water in the alcohol solvent are 0.02-0.7, 0.3-1.5, and 1-16 moles / liter, respectively. (c) The suspension is stirred or sonicated until a coating is formed. (d) The coated powder is washed with alcohol, dried, and then calcined at 200-300°C under air or vacuum.

[0120] Thus, in one embodiment, the main sol-gel coating process comprises: (iiia) providing a mixture of alcohol, ammonia, water, a light-emitting core having a (primer layer and) a main ALD coating layer, and a metal alkoxide precursor, and stirring the mixture, whereby a main sol-gel coating layer is formed on the main ALD coating layer, the metal alkoxide precursor being in particular a titanium alkoxide, a silicon alkoxide, or an aluminum alkoxide; (iiib) recovering from the mixture a luminescent core having (the primer layer) and a primary ALD coating layer and a primary sol-gel coating layer, and optionally heat-treating the recovered luminescent core having the primer layer, the primary ALD coating layer, and the primary sol-gel coating layer to provide a luminescent particle having a hybrid coating.

[0121] Thus, in another embodiment, the primary sol-gel coating process comprises: (ibl) providing a mixture of alcohol, ammonia, water, a luminescent core optionally with a washed layer, in particular the luminescent core and the washed layer (or the luminescent core with the washed layer), and a metal alkoxide precursor while stirring the mixture, wherein a first sol-gel coating layer is formed on the washed layer and / or on the luminescent core without the washed layer, in particular on the washed layer, the metal alkoxide precursor being selected in particular from titanium alkoxide, silicon alkoxide or aluminum alkoxide; (ib2) recovering a luminescent core having the (washed layer and) primary sol-gel coating layer from the mixture, and if necessary, heat-treating the recovered luminescent core having the primary sol-gel coating layer (and the washed layer) to provide a luminescent core having a primer layer thereon.

[0122] The process of recovering the cores (with their respective (coating) layers) from the mixture may, for example, comprise one or more of filtration, centrifugation, decanting (precipitating supernatant liquid). The heat treatment may comprise one or more, in particular both, of drying and calcination, i.e. a stage of drying at a temperature in the range of 70-130°C, followed by a stage of calcination (under air, or under vacuum or (other) inert atmosphere). Thus, during part of the time of the heat treatment, the (coated) luminescent particles may be in an inert environment, such as vacuum, or one or more of N2 and noble gases. The heat treatment is believed to improve the stability of the luminescent material. Furthermore, as mentioned above, in the (main and / or primary) sol-gel coating process, silicon (or other metals; however, the formulae below refer to Si) alkoxides, in particular precursors,

[0123] [ka] where R1, R2, R3 are selected from the group consisting of hydrolyzable alkoxy moieties and R4 is selected from the group consisting of C1-C6 linear alkyl moieties, hydrolyzable alkoxy moieties, and phenyl moieties. Optionally, ligands other than alkoxides may be applied as precursors in the sol-gel process.

[0124] The particles obtained by the sol-gel coating process may contain multiple nuclei if necessary. For example, in the case of quantum dots, aggregates with a (primary and / or main) sol-gel coating may be obtained. Also, the silica precursor (or other metal oxide precursor) thus coats multiple QDs with a thin single shell (in particular with a main ALD coating layer), forming coated aggregates. This may depend, among other things, on the concentration of the quantum dots, etc.

[0125] The precursors of the sol-gel coatings mentioned above have been described in particular with respect to silicon alkoxide precursors. However, aluminum (or other metal) alkoxide precursors may also be applied. Furthermore, a combination of two or more chemically distinct precursors may be applied to provide the sol-gel coating layer or first coating layer.

[0126] The term "sol-gel coating process" may also relate to multiple sol-gel coating processes. Multiple sol-gel coating processes, in particular multiple primary sol-gel coating processes, may provide layers (multilayers) with substantially the same composition throughout the layer thickness (e.g. when each coating stage or step in the (primary) sol-gel coating process comprises depositing substantially the same material) or may provide a multilayer with two or more layers with different compositions, e.g. a stack of two or more (sol-gel) layers, each with two or more different compositions. For example, a SiO2-Al2O3 (sol-gel) multilayer may be provided, e.g. a stack of three or more (sol-gel) layers of alternating SiO2 and Al2O3 (see also above).

[0127] To facilitate the deposition of the main ALD coating layer, the light-emitting core may comprise a primer layer. In one embodiment, the primer layer comprises a primary sol-gel coating layer (optionally including multilayers), in particular provided by a (primary) sol-gel coating process. The primary sol-gel coating layer may facilitate the deposition of a (thin) conformal main ALD coating layer. To further support the deposition of the main ALD coating layer, in one embodiment, the surface of the core is cleaned before providing the primary sol-gel layer and / or the main ALD coating layer.

[0128] In order to facilitate the main ALD deposition process and in particular to allow the deposition of an ALD layer or layers with as few defects as possible, any chemically reactive contaminations (also known as "second phases") that may be present in the powder (in particular the raw material product comprising multiple luminescent cores) may be removed. Preferably, small particles, which usually have submicron dimensions and may adhere to the surface of the phosphor particles (luminescent cores), are sufficiently removed before deposition in the main ALD coating process. Cleaning of the surface of the cores may in particular comprise a (chemical) washing process. In one embodiment, the cores may be washed by applying a washing process, by applying an aqueous liquid. Such an aqueous liquid may comprise an acid or a base or may comprise, for example, water (with a neutral pH). Water may be applied, for example, to remove small undesired particles and part of the second phase. Furthermore, in order to remove additional impurities, the pH of the aqueous liquid may be changed, for example to a pH value of at least 8, in particular to a pH value of at least 9, or to a pH value below 6, in particular to a pH value below 5. In this case, for example, the impurities may be dissolved. In another embodiment, a non-aqueous solvent may be applied, especially to water-sensitive particles (cores). Thus, especially aqueous liquids with additives (e.g., to change the pH), non-aqueous solvents, or combinations of these liquids / solvents may be applied. Thus, the cleaning / washing process may be labeled as a "chemical cleaning process" by using especially a cleaning solvent (including an aqueous liquid).

[0129] In case the chemical stability of the phosphor (the luminescent core) in water, base and / or acid is limited, a washing procedure with very mild conditions may be applied to remove the second phase without dissolving (part of) the phosphor particles. This can be chosen depending on the stability of the phosphor and impurity phases, instead of strong acids, with pK aThis can be achieved by selecting a weak acid with a value of 0.1 to 0.25 (see below). Additional or alternative degradation of the phosphor in the washing process can be avoided by first applying a non-aqueous solvent to the luminescent core (phosphor) to provide a suspension (of luminescent particles / cores) and then adding a weak acid (or base) such that the total amount of water and acid concentration is only sufficient to dissolve the impurity phase.

[0130] A washing solvent with a pH of less than 7 is beneficial for hydrolysis-sensitive luminescent materials, since such luminescent materials disclosed herein react as bases in aqueous media. Such washing solvents may be less acidic. In particular, organic acids, such as acetic acid diluted in polar solvents, such as aliphatic alcohols, such as ethanol or isopropanol as described above, with low proton concentrations may be used as washing solvents. The more sensitive the luminescent material, the more dilute the washing solvent (i.e., the lower the proton concentration) should be, since the goal of the washing process is to remove the basic impurity phase and form a surface of the particulate luminescent material that promotes adhesion of the subsequent primer layer without degrading the luminescent material. Thus, if it is observed that much of the luminescent particulate material degrades or dissolves in the washing process, the amount of degradation may be suppressed by reducing the acid concentration, replacing the solvent with another solvent with a lower dielectric content, and / or cooling the washing suspension.

[0131] After washing, the number of fine particles in the phosphor powder may be further reduced by precipitation in a non-reactive liquid (usually a polar organic solvent, e.g., absolute ethanol, or other alcohol). In some embodiments, ultrasound is applied to the suspension before precipitation to better separate and disperse the fine particles from the larger phosphor particles.

[0132] As a result of the chemical cleaning process, a thin layer may be formed on the surface of the particles (cores) that has a composition different from the normal composition of the luminescent particles (cores). That is, the surface composition of the particulate luminescent particles may differ slightly from the bulk composition of the particulate luminescent material. In particular, the thin layer (i.e. the surface) may have a higher oxygen concentration (content) than the (normal composition of) the luminescent core. In one embodiment, applying a chemical cleaning may provide a cleaning result layer on the luminescent core. The cleaning process may provide a surface (cleaning result layer) that aids in the adhesion of a subsequent primer layer. The thin layer / surface may contain, for example, alkaline earth elements (e.g. strontium), aluminum, and oxides, for example, when a hydrolysis-sensitive luminescent material of the alkaline earth aluminate type disclosed in the present application is coated. The surface layer may contain elements such as lithium, silicon, europium, carbon and / or hydrogen, depending on the luminescent material. The cleaning result layer may in particular include an oxide-containing layer. The cleaning result layer may not necessarily conformally and / or completely cover the surface of the luminescent core (see above regarding the primer layer). The washed layer may not be a continuous layer, for example comprising a plurality of layer sections, each covering only a section of the surface of the light-emitting core. In one embodiment, the washed layer may be evenly distributed over (on) the light-emitting core. In one embodiment, the washed layer may cover at least 30% of the core's surface, for example at least 50%, particularly at least 75%, for example at least 90%, or particularly at least 95% or more, or more particularly at least 99% or more.

[0133] In experiments, it has been found that a washed layer can be observed even when mild cleaning solvents are applied. In particular, in the case of nitride or oxonitride compounds, the O:N ratio can be higher in the washed layer. The luminescent core comprises in particular a nitride or oxonitride compound. In one embodiment, the luminescent material, in particular the luminescent material of the luminescent core, comprises a nitride luminescent material (core). In another embodiment, the luminescent material, in particular the luminescent material of the luminescent core, comprises an oxonitride luminescent material (core).

[0134] Thus, in another embodiment, the method comprises: (ia) applying a chemical cleaning process to provide a resulting layer on the luminescent core, in particular the resulting layer comprises an oxide-containing layer. In another embodiment, applying the chemical cleaning process comprises drying the luminescent core after removing the cleaning solvent. The resulting layer may be provided during cleaning of the luminescent core with the cleaning solvent and / or during drying of the luminescent core. In another embodiment, a primary sol-gel coating is provided after applying the chemical cleaning process (optionally including drying of the luminescent core). Applying the chemical cleaning process may provide a luminescent particle having a resulting layer on the luminescent core.

[0135] Thus, in another embodiment, the method further comprises the step of providing a primary sol-gel coating layer on the luminescent core and the washed layer (or the luminescent core comprising the washed layer) by application of a primary sol-gel coating process, thereby providing a primer layer comprising the washed layer and the primary sol-gel layer, in particular the primer layer having a primer layer thickness (d1) in the range of 0.1 to 5 nm.

[0136] In one embodiment, the cleaning solvent may include an aqueous solvent. This may also be referred to as a "wet chemical cleaning process". In one embodiment, for example, the cleaning solvent includes a strong acid or a strong base. These terms are known in the art. Examples of strong acids are HCl, HBr, HClO4, HI, HNO3. Examples of strong bases are NaOH, KOH, CaOH. In yet another embodiment, the cleaning solvent includes a weak acid or a weak base. Examples of weak acids that may be used are, for example, acetic acid, formic acid, hydrofluoric acid, trichloroacetic acid, citric acid, oxalic acid, etc. Examples of weak bases are, for example, ammonia, sodium bicarbonate, alanine, and methylamine.

[0137] A weak acid or base has a pK (in water at room temperature), a Value or pK bThe values ​​may be selected to be greater than 3, in particular greater than or equal to 4. In one embodiment, the cleaning solvent comprises one or more weak acids selected from the group of acetic acid, formic acid, hydrofluoric acid, trichloroacetic acid, citric acid, oxalic acid. The cleaning solvent may in particular comprise formic acid or acetic acid. In another embodiment, the cleaning solvent comprises one or more weak bases ammonia, sodium bicarbonate, alanine, and methylamine. The cleaning solvent may in particular comprise a combination of a non-aqueous fluid and a weak acid or weak base. For example, in one embodiment, the cleaning solvent may comprise an alcohol (e.g., propanol, isopropyl alcohol, ethanol, (cyclo)hexanol, or any other alcohol having one or more hydroxyl groups) and a weak acid, for example, formic acid and / or acetic acid. Alternatively, in one embodiment, the cleaning solvent may have a mixture of alcohol and polyol. In one embodiment, for example, the cleaning solvent comprises a mixture of ethanol and triethylene glycol, in particular, with a trace of water acting as a dissolution catalyst. Such a combination may be advantageously applied to wash luminescent particles (cores) that may easily decompose under the influence of water. In an embodiment, the washing solvent may contain less than 50% water by weight (based on the weight of the washing solvent). The washing solvent may, for example, contain 40% water by weight or less, such as 35% water by weight or less. In an embodiment, the washing solvent may contain 25% water by weight or less. In particular, the washing solvent (containing a (weak) base or a (weak) acid) contains at least 5% water by weight, such as at least 10% water by weight. In yet another embodiment, the washing solvent is a non-aqueous washing solvent. Furthermore, the application of a weak acid (and weak base) may provide another advantage, that it may provide a pH buffering function. Thus, the robustness of the wet washing process may be improved by using a weak acid or weak base, where the pH of the washing solvent does not change substantially even if an excess of weak acid (or base) is added to the washing solvent (e.g., when not all impurities are removed by the washing solvent).

[0138] Thus, in another embodiment, the chemical cleaning process may include, inter alia: (i) washing the luminescent core by applying a washing solvent (process), said washing solvent comprising a (weak) acid or a (weak) base, in particular a (weak) acid, said washing solvent comprising up to 50% w / w water, in particular in the range of 10-35% w / w water, and optionally (ii) subsequently drying the light-emitting core to provide a light-emitting core including a washed layer thereon; The cleaning process may include a wet chemical cleaning process having

[0139] In particular, based on a cleaning process (including a drying treatment, if necessary), an oxygen-containing layer may be provided on the luminescent particles.

[0140] The different (coating) layers that may be constructed on the luminescent core (primary layer, main ALD layer, main sol-gel coating layer, and further ALD coating layer) are in particular light-transmitting. This means that at least a portion of the light incident on each layer is transmitted through the respective layer. The different (coating) layers may therefore be fully or partially transparent, or semi-transparent. In one embodiment, more than 90% of the (visible) light incident on the (coating) layer is transmitted through the (coating) layer. The (coating) layer may be light-transmitting due to the properties of the material of which it is constructed. For example, the coating layer may be constructed of a transparent material even if the layer is relatively thick. In another embodiment, one or more (coating) layers may be thin enough that each layer is light-transmitting, while the material of which it is constructed may not be transparent or semi-transparent if it is constructed of a relatively thick layer. The materials described herein may all be transparent to (visible) light, or may be constructed with suitable layer thicknesses that are transparent to (visible) light.

[0141] In another embodiment, the present invention provides a lighting device, which comprises a light source configured to generate source radiation, in particular one or more of blue and UV, and a wavelength converter comprising the luminescent material described herein. The wavelength converter is configured to convert at least a portion of the source radiation into wavelength-converted light (e.g. one or more of green, yellow, orange and red light). The wavelength converter is in particular radiatively coupled to the light source. The term "radiatively coupled" means in particular that the light source and the luminescent material are associated with each other such that at least a portion of the radiation emitted by the light source is received by the luminescent material (and at least a portion is converted into luminescence). Thus, the luminescent core of the particle can be excited by the source radiation providing luminescence of the luminescent material in the core. In one embodiment, the wavelength converter comprises a matrix (material) containing the luminescent material (particles). For example, the matrix (material) may comprise one or more materials selected from the group consisting of transparent organic material supports, for example selected from the group consisting of PE (polyethylene), PP (polypropylene), PEN (polyethylene naphthalate), PC (polycarbonate), polymethylacrylate (PMA), polymethylmethacrylate (PMMA) (Plexiglas or Perspex), cellulose acetate butyrate (CAB), silicone, polyvinyl chloride (PVC), polyethylene terephthalate (PET), (PETG) (glycol modified polyethylene terephthalate), PDMS (polydimethylsiloxane) and COC (cycloolefin copolymer). Additionally or alternatively, the matrix (material) may comprise an epoxy resin.

[0142] In forming such lighting devices, the coatings disclosed herein allow for the use of hydrolysis-sensitive phosphors as the luminescent material in the wavelength converter. In particular, luminescent materials that are susceptible to degradation under the conditions used in forming the matrix in which the luminescent particles are embedded to form the wavelength converter can be used in the lighting devices (as shown in FIG. 3 below). For example, alkaline earth aluminate luminescent materials, or luminescent materials having an alkaline earth aluminate type surface layer after the cleaning process disclosed herein. Such hydrolysis-sensitive luminescent materials include, for example, the luminescent particles described above, including SrLiAl3N4:Eu 2+ The luminescent material may be selected from the following (class). If necessary, a part of Sr may be replaced with another alkaline earth metal (group 2 element of the periodic table). For example, the above-mentioned (Sr,Ca)LiAl3N4:Eu, (Sr,Ca,Ba)Li d Mg a Al b N4:Eu, where 0≦a≦4; 0≦b≦4; 0≦d≦4; a+b+d=4 and 2a+3b+d=10, (Sr,Ba)Li2Al 2-z S z O 2-z N 2+z : Eu, where 0≦z≦0.1. Also, for example, the aforementioned SrLi2Al 2-x SiO 2-x N 2+x :Eu, or (Sr,Ca)SiAlN3:Eu. The use of the coatings disclosed herein enables the use of such hydrolysis-sensitive luminescent materials in processes for forming wavelength converters, for example, where the luminescent particles are embedded in a matrix such as a silicone resin and the uncoated luminescent material would otherwise degrade.

[0143] The lighting device may be part of or applied to, for example, an office lighting system, a home application system, a store lighting system, a domestic lighting system, an accent lighting system, a spot lighting system, a theater lighting system, a fiber optic application system, a projection system, a self-illuminated display system, a pixelated display system, a segmented display system, a warning sign system, a medical lighting application system, an indicator sign system, a decorative lighting system, a portable system, a vehicular application, a greenhouse lighting system, a horticultural lighting, or an LCD backlight.

[0144] As mentioned above, the lighting unit may be used as a backlight unit in an LCD display device. Accordingly, the present invention also provides an LCD display device including an lighting unit as described herein configured as a backlight unit. In another embodiment, the present invention also provides a liquid crystal display device including a backlight unit, the backlight unit having one or more lighting devices as described herein.

[0145] The light source is in particular a light source that emits light (light source radiation) in a wavelength range of at least 200-490 nm during operation, in particular a light source that emits light in a wavelength range of at least 400-490 nm during operation, in particular light at 440-490 nm. This light may be used in part by the wavelength conversion nanoparticles (as described further below). Thus, in a particular embodiment, the light source is configured to generate blue light. In a particular embodiment, the light source comprises a solid-state LED light source (such as an LED or a laser diode). The term "light source" may also relate to a plurality of light sources, such as 2-20 (semiconductor) LED light sources. Thus, the term LED may also refer to a plurality of LEDs. The term white light in this application will be clear to the skilled person. This particularly relates to light having a correlated color temperature (CCT) between about 2000-20000K, in particular between 2700-20000K, in particular general lighting in the range of about 2700-20000K, in particular backlighting in the range of about 7000K-20000K, in particular light within about 15 SDCM (standard deviation of color matching) from the BBL (black body locus), in particular within about 10 SDCM from the BBL, in particular within about 5 SDCM from the BBL. In one embodiment, the light source may provide a source radiation having a correlated color temperature (CCT) between about 5000-20000K, for example a direct phosphor converted LED (e.g. a blue light emitting diode with a thin layer of phosphor to obtain 10000K). Thus, in a particular embodiment, the light source is configured to provide a source radiation having a correlated color temperature in the range of 5000-20000K, in particular in the range of 6000-20000K, such as 8000-20000K. The advantage of a relatively high color temperature is that there can be a relatively high blue component in the radiation of the light source.

[0146] The term "control" and similar terms specifically means at least determining an action or supervising the execution of an element. Thus, in this application, "control" and similar terms may refer to, for example, imposing a behavior on an element (determining a behavior or monitoring the execution of an element), etc. For example, measuring, displaying, operating, opening, shifting, changing temperature, etc. Furthermore, "control" and similar terms may additionally include monitoring. Thus, "control" and similar terms may include imposing a behavior on an element, as well as imposing a behavior on an element and monitoring an element. The control of an element is performed by a control system, which may be represented as a "controller". Thus, the control system and the element may be functionally coupled, at least temporarily or permanently. An element may include a control system. In an embodiment, the control system and the element may not be physically coupled. The control may be performed by wired and / or wireless control. The term "control system" may also refer to, for example, imposing a behavior on an element, as well as monitoring an element. It represents a number of different control systems, which may in particular be functionally coupled, for example one control system may be a master control system and one or more other control systems may be slave control systems, and the control systems may have or be functionally coupled to a user interface.

[0147] The control system may also receive and execute commands from a remote control device. In one embodiment, the control system may be controlled via an application on a mobile device such as a smart phone, iPhone, tablet, etc. Thus, a device does not necessarily have to be coupled to the lighting system, but may be functionally (temporarily) coupled to the lighting system.

[0148] Thus, in an embodiment, the control system may (also) be configured to be controlled by an application on a remote device. In such an embodiment, the control system of the lighting system may be a slave control system or a control system in slave mode. For example, the lighting systems may be identifiable by a code, in particular a unique code of each lighting system. The control system of the lighting system may be configured to be controlled by an external control system, which may access the lighting system based on knowledge of the (unique) code (input by a user interface with an optical sensor, for example a QR code reader). The lighting system may also have means to communicate with other systems or devices, such as based on Bluetooth, WIFI, LiFi, ZigBee, BLE, WiMAX, or other wireless technologies.

[0149] A system, apparatus or device may perform an operation in a "mode", "mode of operation", or "mode of operation". Similarly, in a method, an operation, phase or step may be performed in a "mode", "mode of operation", "mode of operation" or "mode of operation". The term "mode" may also be indicated as a "control mode". This does not exclude that the system, apparatus or device may be adapted to provide another control mode or multiple other control modes. Similarly, this does not exclude that one or more other modes may be performed before and / or after performing a mode.

[0150] However, in one embodiment, a control system adapted to provide at least the control mode may be utilized. If other modes are available, the selection of such modes may be performed, inter alia, via a user interface. However, other options are possible, such as the mode being performed depending on a sensor signal or a (time) scheme. Also, in one embodiment, an operational mode may represent a system, equipment, or device that is only operable in a single operational mode (i.e., "on" without needing separate adjustability).

[0151] Thus, in one embodiment, the control system may be responsive to one or more of a user interface input signal, a sensor signal (of a sensor), and a timer, where the term "timer" may refer to a clock and / or a predefined time scheme.

[0152] Embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings in which corresponding reference symbols indicate corresponding parts and in which: [Brief description of the drawings]

[0153] [Figure 1] FIG. 2 is a diagram showing an embodiment of a light-emitting particle; [Figure 2a] FIG. 2 is a schematic diagram illustrating another embodiment of a luminescent particle. [Figure 2b] FIG. 2 is a schematic diagram illustrating another embodiment of a luminescent particle. [Diagram 3] FIG. 1 is a schematic diagram of a lighting device. [Figure 4a] FIG. 1 shows an SEM image of a luminescent particle. [Figure 4b] FIG. 1 shows an EM image of a luminescent particle. [Figure 5a] FIG. 1 illustrates some experimental results comparing embodiments of the present invention with conventional luminescent materials. [Figure 5b] FIG. 1 illustrates some experimental results comparing embodiments of the present invention with conventional luminescent materials. [Figure 6a]FIG. 1 shows a cross section of an array of pcLEDs. [Figure 6b] FIG. 1 shows a top-down schematic of an array of pcLEDs. [Figure 7a] FIG. 1 shows a schematic plan view of an electronic circuit board on which an array of pcLEDs can be mounted. [Figure 7b] FIG. 7b shows an array of pcLEDs mounted on the electronic circuit board of FIG. 7a. [Figure 8a] FIG. 1 shows a schematic cross-section of an array of pcLEDs arranged with respect to a waveguide and a projection lens. [Figure 8b] FIG. 8b shows a similar arrangement to FIG. 8a without the waveguide. [Figure 9] FIG. 1 is a schematic diagram of an example camera flash system that includes an adaptive lighting system; [Figure 10] 1 is a schematic diagram of an example display (e.g., AR / VR / MR) system including an adaptive lighting system. The drawings are not necessarily to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0154] In Fig. 1 an embodiment of a luminescent particle 100 is shown in a schematic manner. The luminescent particle 100 comprises a luminescent core 102 with a primer layer 105 on the luminescent core 102. Here, the luminescent core 102 with the primer layer 105 is also referred to as the luminescent particle 100 with the primer layer 105. The primer layer 105 has a chemical composition different from that of the core 102. The luminescent core 102 comprises, for example, micrometer-sized particles of luminescent nitride or sulfide phosphors. However, it may also comprise other (smaller) materials such as luminescent nanoparticles (see separate Fig. 2b).

[0155] The luminescent particle 100 further comprises a main ALD coating layer 120. In the illustrated embodiment, the main ALD coating layer 120 comprises a multilayer 1120 having three layers 1121, layer 1121a, layer 1121b, and layer 1121c. The three layers 1121a, 1121b, 1121c in particular have (at least two) different chemical compositions. In particular, the adjacently (and in contact) arranged layers 1121 have different compositions. Furthermore, one or more layers 1121 of the multilayer 1120 may have a chemical composition different from the chemical composition of the primer layer 105. The layers 1121 may, in one embodiment, comprise different oxides of, for example, Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V. Additionally or alternatively, the layers 1121 may comprise Si and / or Ge. In particular, one of the layers 1121 may be an alumina layer.

[0156] The luminescent particle 100 further comprises a primary sol-gel coating layer 130, in particular having a different chemical composition than one or more of the layers 1121 of the multilayer 1120. The figure further shows that the primary ALD coating layer 120 is disposed between the primer layer 105 and the primary sol-gel layer 130. In particular, adjacently disposed / contacting coating layers may have different compositions. In the illustrated figure, the layer 1121a in particular has a composition different from that of the primary sol-gel layer 130. The layer 1121c in particular has a composition different from that of the primer layer 105. Thus, the hybrid coating of the embodiment of FIG. 1 comprises the primer layer 105, the primary ALD layer 120, and the primary sol-gel coating layer 130. In another embodiment, for example, see FIG. 2a, the hybrid coating further comprises another ALD coating layer 140.

[0157] The embodiment of FIG. 2a also has a further ALD coating layer 140 arranged on the main sol-gel coating layer 130. In the embodiment shown, the further ALD coating layer 140 (also) has a further multilayer 1140 including two (further sub)layers 1141, 1141a, 1141b (of the further multilayer 1140). In yet another embodiment, the further ALD coating layer 140 is (deposited as) a single layer. In FIG. 2a, the thicknesses of the layers are also shown. It is noted that the thicknesses are not to scale and are shown only to explain the meaning of the terms and to indicate the positions. The thickness of the primer layer is indicated with reference d1. The thickness d1 of the primer layer may be in the range of 0.1 to 5 nm. The thickness of the ALD coating layer is indicated with reference d2. The thickness d2 of the ALD coating layer may in particular be in the range of 5 to 250 nm. The thickness of the main sol-gel coating 130 is indicated with reference d3. The thickness d3 of the main sol-gel coating layer is generally greater than the thickness d2 of the ALD coating layer. The thickness d3 of the main sol-gel coating layer is in particular in the range of 50-700 nm. The embodiment shown has a multilayer 1120 with three layers 1121, each layer 1121 having a layer coating thickness d21 in the range of 1-20 nm. In the embodiment shown, the layer coating thicknesses d21 of the three layers 1121 are approximately the same. However, the layer coating thickness d21 may vary between the different layers 1121. See, for example, FIG. 4b. The three layers 1121a, 1121b, and 1121c may, for example, represent alternating layers of Al2O3 layers (e.g. 1121b) and Ta2O5 layers (e.g. 1121a, 1121c). The thickness (not represented by a reference number) of the (another sub-)layer coating layer of the (another sub-)layer 1141 of the other multilayer 1140 may be within the range indicated, in particular with respect to the thickness d21 of the layer coating layer of the layer 1121 of the multilayer 1120.

[0158] 2a further shows the primer layer 105 diagrammatically having an oxide-containing layer 101 and a primary sol-gel layer 110. The oxide-containing layer 101 is disposed on the surface 67 of the core 102. In one embodiment, the oxide-containing layer 101 and the primary sol-gel layer 110 are continuous and conformal. In yet another embodiment, this may differ, for example, the main ALD coating layer 120 may contact the oxide-containing layer 101 in some places and may contact the surface 67 of the core in other places (while the primary sol-gel layer 110 contacts in other places).

[0159] Furthermore, in FIG. 2a, the references 17, 27, 37, 47, 57 are used to denote the surfaces of the respective layers, and the reference 67 is used to denote the surface of the core 102. As mentioned above, the layer thicknesses mentioned in the present application are in particular average layer thicknesses. In particular, at least 50%, in particular at least 80%, of the area of ​​the respective layers have such indicated layer thickness. Thus, referring to the thickness d2 between the surface 47 and the surface 37, less than at least 50% of the surface 37, layer thicknesses in the range of, for example, 5 to 250 nm are recognized, other layer thicknesses, for example less than at least 50% of the surface area 37, for example smaller or larger thicknesses are recognized. However, the average d2 of the main ALD coating layer (multilayer) 120 is within the indicated range of 5 to 250 nm. Similarly, this may also apply to other thicknesses indicated in the present application. For example, referring to the thickness d3 between surface 37 and surface 27, this thickness is in the range of 50-700 nm over at least 50% of the area 27, while other thicknesses are less than 50% of the surface area 27, e.g. smaller or larger thicknesses are permitted, except that the average d1 of the first layer, the main sol-gel layer 130, is in the indicated range of 50-700 nm, in particular e.g. 100-500 nm.

[0160] Fig. 2b shows a schematic embodiment in which the luminescent core 102 comprises luminescent nanoparticles. Here, quantum dots 160 are used as an example. The quantum dots in this example comprise quantum rods with a (semiconductor) core material 161 such as ZnSe and a shell 162 such as ZnS. Of course, other luminescent nanoparticles can also be used. Such luminescent quantum dots 160 can also be provided with a hybrid coating.

[0161] 1-2 show diagrammatically luminescent particles 100 with a single core. However, if necessary, aggregates surrounded by a hybrid coating may also be found. This may apply in particular to quantum dots as luminescent particles defining a luminescent core 102.

[0162] The figures show in particular an embodiment of a coating structure on the phosphor particles or luminescent cores 102 (after application of the respective (ALD and sol-gel) coating processes). The phosphor particles 102 may be covered with an oxide layer 101 formed by a washing and baking process. In one embodiment, the primary sol-gel coating 110 comprises silicon oxide (SiO2) provided by a (primary) sol-gel coating process. The first SiO2 layer 110 acts as a nucleation or seed layer for the main ALD coating layer 120 provided by a primary atomic layer deposition process in particular. Thus, the primary sol-gel coating layer 110 does not need to form a conformal or completely filled coating around each core 102 (similar to the primary layer 105). The primary sol-gel coating layer 110, e.g. the primary SiO2 layer 110, can also be seen as a surface treatment, providing OH groups on the phosphor particles 102. Such OH- groups help the ALD precursors to bind to the surface, thus initiating film growth.

[0163] The main ALD coating layer 120 has, inter alia, a multilayer 1120, also referred to as a "nanolaminate" 1120, of metal oxide (sub) layers 1121. The nanolaminate 1120 may form a highly dense, nearly pinhole-free conformal coating on the phosphor particles that is nearly impermeable to gases such as water vapor and oxygen. In one embodiment, the nanolaminate protective layer 1120 may have a thickness d2 of 20-50 nm, consisting of two or more sublayers of Al2O3, TiO2, ZrO2, HfO2, SnO2, ZnO, or Ta2O5. Each layer 1121 may have a thickness d21 in the range of 1 nm to 15 nm. In one embodiment, the outer layer 1121, i.e., the layer in contact with the main sol-gel coating layer 130 (1121a in Figures 1 and 2a), is a chemically stable layer, such as HfO2, ZrO2 or Ta2O5, that does not corrode when exposed to water or other solvents such as cyclohexanone.

[0164] The primary sol-gel coating layer 130 may also include silicon oxide (SiO2) provided by a (primary) sol-gel coating process, similar to the primary sol-gel coating layer 110. The primary sol-gel coating 130 may, among other things, act as a mechanical protection and prevent damage to the underlying barrier coating 120. In the LED manufacturing process, the phosphor particles undergo various process steps such as mixing, sieving, pressing, and molding. These process steps may induce mechanical stresses in the coating. As a result, the coating may be damaged. The primary sol-gel coating layer 130 provides high robustness against post-processing and manufacturing steps. In one embodiment, applying the primary sol-gel coating layer 130 on the luminescent particles 100 can ensure high reliability.

[0165] In one embodiment of the present invention, another ALD coating layer 140 is added to the layer architecture, as shown in FIG. 2a. The another ALD coating layer 140 in one embodiment has a nanolaminate 1140. The layer 140 or multilayer 1140 may include metal oxides such as Al2O3, TiO2, ZrO2, HfO2, SnO2, ZnO, or Ta2O5. The total thickness d4 of the layer 140 is in the range of 10-50 nm, among others. The another ALD coating layer 140 may further stabilize the overall coating structure by filling pores and pinholes in the main sol-gel coating layer 130. The another ALD coating layer 140 may also suppress the surface reactivity of the main sol-gel layer 130. This surface reactivity may be significant in maintaining the rheology or other properties of a particular silicone phosphor slurry in one embodiment of the LED manufacturing process.

[0166] 3 shows a schematic of an illumination device 20 comprising a light source 10 configured to generate source radiation 11, in particular one or more of blue and UV, and a wavelength converter 30 comprising a luminescent material 1 with particles 100 as described herein. The wavelength converter 30 comprises a matrix, for example a silicone or organic polymer matrix as described above, in which the coated particles 100 are embedded. The wavelength converter 30 is configured to convert (wavelength) at least a portion of the source radiation 11 into wavelength-converted light 31. If necessary, the source radiation 11 may also pass through the wavelength converter 30 (unconverted).

[0167] The wavelength-converted light 31 includes at least the emission from the coated particle 100 described herein. However, the wavelength converter 30 may optionally have one or more other luminescent materials. The wavelength converter 30, particularly the luminescent material 1, may be disposed at a non-zero distance d30, such as a distance of 0.1-100 mm. However, the distance d30 may be zero, if desired, for example, if the luminescent material is embedded in a dome on the LED die. The distance d30 is the shortest distance between the light emitting surface of the light source 10, such as the LED die, and the wavelength converter 30, particularly the luminescent material 1.

[0168] The light source 10 may be an LED, for example, the lighting device 20 is a phosphor-converted LED ("pcLED"). For example, the light source 10 may be a III-nitride LED that emits ultraviolet, blue, green, or red light. LEDs formed from any other suitable material system and emitting light at any other suitable wavelengths may also be used. Other suitable material systems may include, for example, III-phosphide materials, III-arsenide materials, and II-VI materials.

[0169] In Fig. 4a an SEM image of a luminescent material 1 comprising a certain coated luminescent particle 100 is shown. In Fig. 4b a TEM image of the coated luminescent particle 100 is clearly shown. The core 102 is provided with an oxide-containing layer 101, a primary (SiO2) sol-gel coating layer 110, a multilayer 1120 consisting of two Al2O3 layers 1121b and two Ta2O5 layers 1121a, and a (SiO2) main sol-gel coating layer 130.

[0170] 5a-5b show some experimental results, in which a coated luminescent particle 100 of the present invention (here comprising SrLiAl3N4:Eu) is compared with a corresponding conventional luminescent particle, which also comprises an ALD coating layer and a sol-gel coating layer. However, the sol-gel coating layer is disposed directly on the surface of the luminescent core 102, and the ALD coating layer is constructed on the sol-gel coating.

[0171] In Fig. 5a, the (normalized) light output over time (Y-axis) is shown, specifically for each luminescent particle in silicone (X-axis). During the experiment, the particles were maintained at 130°C and 100% relative humidity. The circle markers indicate the luminescent particles of the present invention 100, and the square markers indicate conventional luminescent particles.

[0172] In Fig. 5b, the failure probability of the white LED with each luminescent particle is provided after each LED is maintained at 85°C and 85% relative humidity for more than 500 hours. The square markers indicate the luminescent particle 100 of the present invention, and the circle markers indicate the conventional luminescent particle. It should be noted that the probability is shown in percentage on the Y-axis of logarithmic scale. The color point shift in Δu'v' (often also indicated as "(du'V')" or "duv") is given on the X-axis. The (LED including) luminescent particle 100 of the present invention clearly shows less color shift (Δu'v' is calculated as the Euclidean distance between a pair of chromaticity coordinates in the (u',v') CIE 1976 color space).

[0173] The present invention therefore relates to a method for improving the barrier properties of phosphor particle coatings, which is generally applicable to a variety of phosphor particles, but is particularly suited to narrow band red emitting phosphors of the nitride type, e.g., nitride aluminates or oxonitride aluminates, due to their high sensitivity to moisture.

[0174] 6A-6B show cross-sectional and top views, respectively, of an array 600 of pcLEDs 610. The pcLEDs 610 may be structured as an illumination device 20, as shown in FIG. 3, with wavelength converters 30 including coated light-emitting particles 100 included in phosphor pixels 606, with semiconductor diodes 612 disposed on a substrate 602. Such an array may have any suitable number of pcLEDs arranged in any suitable manner. In the illustrated embodiment, the array is shown as being monolithically formed on a shared substrate. However, the array of pcLEDs may instead be formed of separate individual pcLEDs. The substrate 602 may include CMOS circuitry to drive the LEDs, if necessary, and may be formed from any suitable material.

[0175] 6A-6B show a 3×3 array of 9 pcLEDs, but such an array may include, for example, tens, hundreds, or thousands of LEDs. Individual LEDs (pixels) may have a width (e.g., lateral length) in the plane of the array of, for example, 1 millimeter (mm) or less, 500 microns or less, 100 microns or less, or 50 microns or less. LEDs in such an array may be spaced apart from one another by streets or lanes that are, for example, hundreds of microns, 100 microns or less, 50 microns or less, 10 microns or less, or 5 microns or less in width in the plane of the array. Although the illustrated example shows rectangular pixels arranged in a symmetric matrix, the pixels and array may have any suitable shape or arrangement.

[0176] LEDs having dimensions (e.g., sides) in the plane of the array of about 50 microns or less are commonly referred to as micro LEDs, and an array of such micro LEDs may be referred to as a micro LED array.

[0177] The array of LEDs, or a portion of such an array, may be formed as a segmented monolithic structure, with the individual LED pixels being electrically isolated from one another by trenches and / or insulating materials, although the electrically isolated segments may remain physically connected to one another by portions of the semiconductor structure.

[0178] Individual LEDs in an LED array may be individually addressable, addressable as part of a group or subset of pixels in the array, or non-addressable. Light-emitting pixel arrays are therefore beneficial for any application that requires or benefits from fine-granular, spatial, and temporal control of light distribution. These applications may include, but are not limited to, precise special patterning of emitted light from pixel blocks or individual pixels. Depending on the application, the emitted light may be spectrally distinct, adaptive over time, and / or environmentally responsive. Such light-emitting pixel arrays may provide pre-programmed light distributions with various intensities, spatial or temporal patterns. The emitted light may be used for optical wireless communication, based at least in part on received sensor data. Associated electronics and optics may be differentiated at the pixel, pixel block, or device level.

[0179] As shown in Figures 7A-7B, the pcLED array 600 may be mounted on an electronic circuit board 700 having a power and control module 702, a sensor module 704, and an LED mounting area 706. The power and control module 702 receives power and control signals from an external source and from the sensor module 704 based on which the power and control module 702 controls the operation of the LEDs. The sensor module 704 may receive signals from any suitable sensor, for example a temperature sensor or a light sensor. Alternatively, the pcLED array 600 may be mounted on a separate board (not shown) from the power and control module and the sensor module.

[0180] Individual pcLEDs may be introduced or arranged in combination with lenses or other optical elements, if desired, disposed adjacent to or above the phosphor layer. Such optical elements may be referred to as "primary optical elements" although not shown in the figures. Additionally, as shown in Figures 8A-8B, the pcLED array 600 (e.g., mounted on an electronic circuit board 700) may be arranged in combination with secondary optical elements, such as a waveguide, a lens, or both, for use in an intended application. In Figure 8A, light emitted by the pcLEDs 610 is collected by a waveguide 802 and directed to a projection lens 804.

[0181] The projection lens 804 may be, for example, a Fresnel lens. This arrangement is suitable for use, for example, in vehicle headlights. In FIG. 8B, the light emitted by the pcLEDs 610 is directly focused by the projection lens 804 without the use of an intervening waveguide. This arrangement is particularly suitable when the pcLEDs can be placed close enough to each other, and can also be used for camera flash applications and vehicle headlights. For example, optical arrangements similar to those shown in FIGS. 8A-8B may be used in micro LED display applications. In general, any suitable arrangement of optical elements may be used in combination with the LED arrays described herein, depending on the desired application.

[0182] An array of independently operable LEDs may be used in combination with a lens, lens system, or other optical system (e.g., as described above) to provide lighting that can be adapted for a particular purpose. For example, such an adaptive lighting system may provide lighting that varies in color and / or intensity across an illumination scene or object during operation and is directed in a desired direction. A controller is configured to receive data indicative of the placement and color characteristics of objects or people in the scene, and based on that information controls LEDs in the LED array, lighting adapted to the scene is provided. Such data may be provided, for example, by an image sensor, or optical sensors (e.g., laser scanning) or non-optical sensors (e.g., millimeter radar). Such adaptive lighting is becoming increasingly important in vehicle, mobile device camera, VR, and AR applications.

[0183] 9 shows a schematic of an exemplary camera flash system 900 with an LED array and lens system 902, which may be similar or the same as the systems described above. The flash system 900 also includes an LED driver 906, which is controlled by a controller 904, such as a microprocessor. The controller 904 is also coupled to a camera 907 and a sensor 908, and may operate according to instructions and profiles stored in a memory 910. The camera 907 and adaptive lighting system 902 may be controlled by the controller 904 to adapt their field of view.

[0184] The sensors 908 may include, for example, position sensors (e.g., gyroscopes and / or accelerometers) and / or other sensors that can be used to determine the position, velocity, and orientation of the system 900. Signals from the sensors 908 are provided to the controller 904 and used to determine a preferred path of motion for the controller 904 (e.g., which LEDs are currently illuminating the target, which LEDs will illuminate the target after a predetermined time, etc.).

[0185] In operation, illumination from some or all of the pixels of the LED array at 902 may be adjusted, deactivated, operated at full intensity, or operated at intermediate intensities. Beam focusing or steering of the light emitted by the LED array at 902 may be performed electronically by activating one or more subsets of the pixels, allowing dynamic adjustment of the beam shape without moving optical elements or changing the focus of lenses in the lighting fixture.

[0186] FIG. 10 shows a schematic diagram of an exemplary display (e.g., AR / VR / MR) system 1000. It has an adaptive light emitting array 1010, a display 1020, a light emitting array controller 1030, a sensor system 1040, and a system controller 1050. The sensor system 1040 is provided with control inputs, while the system controller 1050 is provided with power and user data inputs. In some embodiments, the modules included in the system 1000 are compactly arranged in a single structure, or one or more elements may be mounted separately and connected via wireless or wired communication. For example, the light emitting array 1010, the display 1020, and the sensor system 1040 may be mounted in a headset or glasses, with the light emitting controller and / or the system controller 1050 mounted separately.

[0187] The light emitting array 1010 may include one or more adaptive light emitting arrays as described above, for example, used to project light into graphic or object patterns that may support AR / VR / MR systems. In one embodiment, an array of micro LEDs may be used.

[0188] The system 1000 can incorporate a wide range of optics into the adaptive light emitting array 1010 and / or the display 1020 , for example, where light emitted by the adaptive light emitting array 1010 is coupled into the display 1020 .

[0189] The sensor system 1040 may include external sensors such as a camera, depth sensor, or audio sensor to monitor the environment, as well as internal sensors such as an accelerometer or a two- or three-axis gyroscope to monitor the AR / VR / MR headset position. Other sensors may include, but are not limited to, air pressure sensors, stress sensors, temperature sensors, or any other suitable sensors required for local or remote environmental monitoring. In some embodiments, the control input may include a detected touch or tap, gesture input, or control based on the headset or display position. In response to data from the sensor system 1040, the system controller 1050 may send images or instructions to the light emitting array controller 1030. Also, changes or modifications to the images or instructions may be implemented by user data input or automatic data input, as needed. User data input may include, but is not limited to, voice commands, haptic feedback, eye or pupil placement, or provided by a connected keyboard, mouse, or game controller.

[0190] In one embodiment, the present invention provides a wet chemical cleaning process (including a drying step) of the powder phosphor (light emitting core) to form an outer particle layer of oxide. Further, a (primary) sol-gel process deposits a primary (SiO2) sol-gel layer, providing a primary sol-gel layer with a thickness in the range of 0.5-5 nm. Then, a multilayer is deposited by ALD, in one embodiment the total ALD coating layer thickness d2 is in the range of 20-50 nm, and the (sub)layer thickness d21 of the layer 1121 of the multilayer 1120 is in the range of 1-20 nm. The multilayer 1120 is composed of two or more metal oxides, such as Al2O3, TiO2, ZrO2, HfO2, SnO2, ZnO, Ta2O5, among others. Then, a (main) sol-gel process may deposit a third layer, e.g. a main sol-gel coating layer 130 of SiO2, with a thickness in the range of 100-500 nm. In yet another embodiment, the fourth layer 140 may be deposited by another ALD process. In an embodiment, the another ALD coating layer 140 may have a total thickness d4 of 5-50 nm, and may in particular have a multilayer with sublayer thicknesses in the range of 1-20 nm. In an embodiment, the multilayer is composed of one or more metal oxides, such as Al2O3, TiO2, ZrO2, HfO2, SnO2, ZnO, Ta2O5.

[0191] (experiment) The effectiveness of the new coating structure of the present invention was evaluated by forming luminescent particles having a hybrid coating as disclosed herein.

[0192] (Polyol washing process) The composition is Sr 0.995 Li2Al 1.995 S 0.005 O 1.995 N 2.005 :EU 0.005A 10.3 g sample of raw phosphor powder was mixed with 30.0 g of ethanol and 30.0 g of triethylene glycol. The suspension had a total moisture content ranging from 0.05 to 0.1% during ultrasonication and treatment at 80 °C for 16 h in a closed pressure vessel. After cooling to room temperature, the phosphor powder was washed with ethanol and dried at 100 °C under ambient atmosphere.

[0193] (Mixed solvent acetic acid washing process) 200-250g of SrLiAl3N4:Eu 0.007 was stirred in 837 g of isopropanol. Under stirring, 560 g of 18.5 wt % acetic acid was slowly added. The suspension was further stirred for a total of 40 min (including acid addition). After 30 min of precipitation, most of the supernatant was removed by decantation, then filtered and rinsed with acetic acid / isopropanol mixture and isopropanol. The washed phosphor was finally dried overnight in vacuum at 50 °C.

[0194] (Thin amorphous silica layer (<5nm)) In this experiment, a primary sol-gel coating layer was provided. 200 g of phosphorus powder (normally washed) was stirred in 960 g of ethanol. 3.5 g of tetraethyl orthosilicate was added to this suspension and stirred for 10 min under ultrasonication. 90 g of 25% by weight aqueous ammonia was added and stirring was continued for another 20 min under ultrasonication. Fines including nano-sized silica particles formed as by-product were removed by precipitation and decantation three times in ethanol. The coated powder was dried overnight at 50° C. under vacuum. After dry sieving (mesh size 100 μm), the coating was cured by heating the powder to 300° C. under vacuum for 10 h.

[0195] (ALD nanolaminate (~25nm)) The main ALD coating layer containing the ALD stack was then deposited on the primer layer containing phosphor particles (including SrLiAl3N4:Eu) in a Picosun Oy ALD R200 reactor. The precursor materials were trimethylaluminum and H2O to form the Al2O3 film and (tert-butylimido)tris(ethylmethylamino)tantalum(V) and H2O to form the Ta2O5 film. The deposition temperature was set at 250 °C. The nitrogen gas purge time between precursor pulses was 60 s. The nanolaminate was composed of 2 × Al2O3 / Ta2O5 sublayers with a total thickness of about 25 nm.

[0196] (Thick amorphous silica layer (~170nm)) In this experiment, luminescent particles were provided with a primary sol-gel coating layer. 85 g of powder (usually after ALD coating) was stirred in 672 g of ethanol for 15 min under ultrasound. To this suspension, 1) 116 g of 25 wt % aqueous ammonia was quickly added (<30 s) and 2) a solution of 68 g of tetraethyl orthosilicate in 408 g of ethanol was added dropwise (~45 min). After complete addition of the alkoxide precursor, the suspension was further stirred for 30 min without ultrasound treatment.

[0197] Fines, including submicron-sized silica particles formed as a by-product, were removed by precipitation and decantation three times in ethanol. The coated powder was dried overnight at 50° C. in vacuum. After dry sieving (mesh size 63 μm), the coating was cured by heating the powder at 300° C. under vacuum for 10 hours.

[0198] An EM image of a portion of a particle is shown in Figure 4(a), and a TEM image of the particle is shown in Figure 4(b).

[0199] (Comparative Test) The prepared particles in silicone were subjected to stress testing and compared to control particles, i.e., particles containing a conventional coating structure, in which the light-emitting particles are first coated with a relatively thick sol-gel coating and then coated with a thin ALD coating. In the stress testing, the particles were held at 130° C. and 100% relative humidity while the light output was measured over time.

[0200] The prepared particles were then placed in a white LED and stressed for 500 hours at 85° C. and 85% relative humidity. The failure probability of the white LED with the luminescent particles according to the present invention was compared with that of the white LED with a conventional coating structure subjected to the same stress test (control LED).

[0201] The results are shown in Figures 5a-5b, which show significantly improved suppression of light output after 60 hours of stress testing, i.e., less than 5% reduction compared to over 50% reduction for the control particles, and the color shift (Δu'v') was substantially minimized compared to the control LED.

[0202] The term "plurality" refers to two or more than two.

[0203] In this application, the terms "substantially" or "essentially" and similar terms will be understood by those skilled in the art. The terms "substantially" or "essentially" may also have embodiments such as "entirely", "completely", "all". Thus, in one embodiment, the adjectives substantially or essentially may be removed. Also, where applicable, the terms "substantially" or "essentially" may refer to 90% or more, such as 95% or more, particularly 99% or more, more particularly 99.5% or more, including 100%.

[0204] Additionally, the term "comprising" includes embodiments where the term "comprising" means "consisting of."

[0205] In particular, the term "and / or" refers to one or more of the items listed before and after it. For example, the phrase "item 1 and / or item 2" and similar phrases may refer to one or more of item 1 and item 2. In one embodiment, the term "comprising" refers to "consisting of," while in another embodiment, it may mean "including at least the specified species, and optionally one or more other species."

[0206] Moreover, the terms first, second, third, etc. in the specification and claims are used to distinguish between similar elements and are not necessarily used to describe a sequential or chronological order. The terms so used are interchangeable, under appropriate circumstances, with it being understood that the embodiments of the invention described herein are capable of operating in sequences other than those described or illustrated herein.

[0207] In the present application, a device, apparatus, or system may be specifically described in operation. As will be apparent to one skilled in the art, the present invention is not limited to methods of operation or to devices, apparatus, or systems in operation.

[0208] It should be noted that the above-described embodiments are illustrative rather than limiting of the invention, and that those skilled in the art can design many alternative embodiments without departing from the scope of the appended claims.

[0209] In the claims, any reference signs placed between parentheses shall not be construed as limiting the claim.

[0210] The use of the verb "to comprise" and its conjugations does not exclude the presence of elements or steps other than those recited in a claim. Unless the context otherwise requires, throughout the specification and claims, the words "comprise", "comprising", and the like, are to be construed in an inclusive sense rather than an exclusive or exhaustive sense, i.e., "including, but not limited to".

[0211] The article "a" or "an" preceding an element does not exclude the presence of a plurality of such elements.

[0212] The invention may be implemented by means of hardware comprising several distinct elements, and by means of a suitably programmed computer. If several means are enumerated in a device, apparatus or system claim, several of these means may be embodied by one and the same item of hardware. The mere fact that certain means are recited in mutually different dependent claims does not indicate that a combination of these means cannot be used to advantage.

[0213] The present invention also provides a control system capable of controlling an apparatus, device or system or capable of implementing a method or process as described herein. Additionally, the present invention provides a computer program product which, when run on a computer operatively coupled to or configured with an apparatus, device or system, controls one or more controllable elements of such an apparatus, device or system.

[0214] Furthermore, the present invention applies to an apparatus, device or system having one or more of the features described in the specification and / or shown in the accompanying drawings.Furthermore, the present invention relates to a method or process having one or more of the features described in the specification and / or shown in the accompanying drawings.

[0215] The various aspects discussed in this patent can be combined to provide different advantages. Moreover, those skilled in the art will appreciate that the embodiments can be combined, and that two or more embodiments can be combined. Furthermore, some of the features may form the basis of one or more divisional applications.

Claims

1. 1. A method for providing a luminescent particle having a hybrid coating, comprising: (i) providing a particulate luminescent material having a surface; (ii) forming a primer layer directly on at least a portion of said surface, said primer layer being a primary sol-gel layer having a thickness in the range of 0.1 to 5 nm; (iii) performing a first atomic layer deposition process to deposit a first ALD layer on the particulate luminescent material having the primer layer, the first atomic layer deposition process using a first precursor of a metal oxide, the first precursor being selected from a group of metal oxides including Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V; (iv) performing a second atomic layer deposition process to deposit a second ALD layer on the first ALD layer, the second atomic layer deposition process using a second precursor of a metal oxide different from the first precursor, the second precursor being selected from a group of metal oxides including Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V; (v) performing a primary sol-gel coating process to form a primary sol-gel coating layer directly on the second ALD layer, the primary sol-gel coating layer having a different chemical composition than the first ALD layer and the second ALD layer; having The method, wherein the step of directly forming the primer layer on at least a portion of the surface of the particulate luminescent material includes subjecting the particulate luminescent material to a primer sol-gel coating process, wherein a metal alkoxide precursor is used in the primer sol-gel coating process.

2. The primer sol-gel coating process comprises: suspending the particulate luminescent material in an alcohol-aqueous ammonia mixture; adding the metal alkoxide precursor to the mixture; agitating the mixture including the metal alkoxide until the primer layer is formed; washing the particulate light-emitting material having the primer layer with alcohol; drying the particulate luminescent material having the primer layer; 2. The method of claim 1, comprising:

3. The method of claim 1 , wherein the metal alkoxide precursor is a silicon alkoxide.

4. The method of claim 1 , further comprising the step of washing the particulate luminescent material in a washing solvent before forming the primer layer, the washing solvent having a pH<7.

5. The method of claim 4 , wherein the washing solvent comprises an organic acid.

6. The method of claim 4 , wherein the wash solvent comprises an aliphatic alcohol.

7. the wash solvent comprises a weak acid and up to 50% wt / wt water; The step of washing the particulate light-emitting material further comprises: subjecting the particulate light-emitting material to a drying treatment continuously; 5. The method of claim 4, having the following structure:

8. (i) the primer layer has a primer layer thickness (d1) in the range of 0.1 to 5 nm; (ii) the first ALD layer and the second ALD layer form a main ALD coating layer, the main ALD coating layer having a main ALD coating layer thickness (d2) in the range of 5 to 250 nm; The method of claim 1, wherein (iii) the primary sol-gel coating layer has a primary sol-gel coating layer thickness (d3) in the range of 50 to 700 nm.

9. the first precursor of the metal oxide is Al; 2. The method of claim 1, wherein the second precursor of the metal oxide is selected from metal oxides including Al, Hf, Ta, Zr, and Ti.

10. The main sol-gel coating process comprises: providing a mixture of alcohol, ammonia, water, the particulate light-emitting material having the primer layer, the first ALD layer, and the second ALD layer, and a metal alkoxide precursor while stirring the mixture, wherein a primary sol-gel coating layer is formed directly on the second ALD layer, and the metal alkoxide precursor is a titanium alkoxide, a silicon alkoxide, and / or an aluminum alkoxide; recovering the particulate luminescent material having the primer layer, the first ALD layer, the second ALD layer, and the primary sol-gel coating layer from the mixture, and subjecting the recovered particulate luminescent material having the primer layer, the first ALD layer, the second ALD layer, and the primary sol-gel coating layer to a heat treatment; 2. The method of claim 1, comprising:

11. In the primary sol-gel coating process, a silicon alkoxide precursor is used, The silicon alkoxide precursor is 【Chemistry 1】 is selected from the group consisting of In the first and second atomic layer deposition processes, Al(CH 3 ) 3 , HAl(CH 3 ) 2 , Hf(N(CH 3 ) 2 ) 4 , Hf(N(CH 2 CH 3 ) 2 ) 4 , Hf[N(CH 3 ) (CH 2 CH 3 ) ] 4 , TaCl 5 , Ta(N(CH 3 ) 2 ) 5 , Ta{[N(CH 3 ) (CH 2 CH 3 ) ] 3 N(C(CH 3 ) 3 )}, ZrCl 4 , Zr(N(CH 3 ) 2 ) 4 , TiCl 4 , Ti(OCH 3 ) 4 , Ti(OCH 2 CH 3 ) 4 a first precursor of the metal oxide and a second precursor of the metal oxide selected from the group consisting of: 2 O and O 3 The method of claim 1, wherein an oxygen source selected from the group consisting of:

12. providing successively n additional ALD layers between the first ALD layer and the second ALD layer, where 2≦n≦10; each additional ALD layer has an additional ALD layer coating layer thickness (d21) in the range of 1 to 20 nm; One or more additional ALD layers are 2 , ZrO 2 , TiO 2 , Ta 2 O 5 The metal oxides include one or more metal oxides selected from the group consisting of One or more additional ALD layers are 2 O 3 Including, The second ALD layer is HfO 2 , ZrO 2 , TiO 2 , Ta 2 O 5 The method of claim 1, further comprising one or more metal oxides selected from the group consisting of:

13. providing another ALD coating layer on the primary sol-gel coating layer by applying another atomic layer deposition process; In the alternative atomic layer deposition process, the alternative metal oxide precursor is selected from the group of metal oxides including Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V; the another ALD coating layer has another ALD coating layer thickness (d4) in the range of 10 to 50 nm; 10. The method of claim 1 , wherein the separate ALD coating layer has a different chemical composition than a chemical composition of the primary sol-gel coating layer.

14. the separate ALD coating layer has two or more layers with different chemical compositions; One or more of the layers may be Al 2 O 3 , TiO 2 , ZrO 2 , HfO 2 , SnO 2 , ZnO and Ta 2 O 5 and a metal oxide selected from the group consisting of The method of claim 13, wherein the two or more layers have a chemical composition different from a chemical composition of the main sol-gel coating layer.

15. The method of claim 1 , wherein the surface of the particulate luminescent material comprises an alkaline earth element, aluminum, and oxygen.

16. 16. The method of claim 15, wherein the alkaline earth element comprises strontium.

17. The particulate light-emitting material is (Ml)Li d Mg a Al b N 4 : Eu, where 0≦a≦4; 0≦b≦4; 0≦d≦4, M1 includes one or more from the group consisting of Ca, Sr, and Ba, and a+b+d=4 and 2a+3b+d=10; and (M2) Li 2 Al 2-z S z O 2-z N 2+z : Eu, where 0≦z≦0.1, and M2 includes one or more of the group consisting of Sr and Ba; 2. The method of claim 1, selected from the group consisting of:

18. The particulate light-emitting material is (i) SrLiAl 3 N 4 :EU 2+ Class, and (ii) SrLi 2 To the 1.995 Yeah 0.005 EITHER 1.995 N 2.005 :Eu 2+ クラス 2. The method of claim 1, selected from the group consisting of:

19. The method of claim 1 , wherein the particulate luminescent material has a number average particle size in the range of 0.1 to 50 μm.

20. A luminescent material comprising luminescent particles obtained by the method according to claim 1.

21. A light-emitting material comprising: a particulate light-emitting material having a surface; a primer layer disposed in contact with the surface of the particulate luminescent material, the primer layer being a primary sol-gel layer having a primer layer metal oxide having a thickness in the range of 0.1 to 5 nm; a first ALD layer disposed on the primer layer and in contact with the primer layer and any portions of the surface of the particulate light-emitting material not covered by the primer layer, the first ALD layer comprising a first oxide of one or more of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V, different from the primer layer metal oxide; a second ALD layer disposed on and in contact with the first ALD layer, the second ALD layer comprising a second oxide of one or more of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V, different from the first oxide, the first ALD layer and the second ALD layer forming a main ALD layer having a thickness in the range of 5 to 250 nm; and a primary sol-gel coating layer disposed on the second ALD layer, the primary sol-gel coating layer having a primary sol-gel coating layer thickness (d3) in the range of 50 to 700 nm and having a different chemical composition than the first ALD layer and the second ALD layer; The luminescent material comprising:

22. 22. The luminescent material of claim 21, wherein at least a portion of the surface of the particulate luminescent material comprises an oxide.

23. 23. The luminescent material of claim 22, wherein at least a portion of the surface of the particulate luminescent material comprises an alkaline earth element and aluminum.

24. 24. The luminescent material of claim 23, wherein the alkaline earth element comprises strontium.

25. The particulate light-emitting material is (Ml)Li d Mg a Al b N 4 : Eu, where 0≦a≦4; 0≦b≦4; 0≦d≦4, M1 includes one or more from the group consisting of Ca, Sr, and Ba, and a+b+d=4 and 2a+3b+d=10; and (M2) Li 2 Al 2-z S z O 2-z N 2+z : Eu, where 0≦z≦0.1, and M2 includes one or more of the group consisting of Sr and Ba; 22. The luminescent material of claim 21, selected from the group consisting of:

26. The particulate light-emitting material is (i) SrLiAl 3 N 4 :EU 2+ Class, and (ii) SrLi 2 To the 1.995 Yeah 0.005 EITHER 1.995 N 2.005 :Eu 2+ クラス 22. The luminescent material of claim 21, selected from the group consisting of:

27. further comprising another ALD coating layer disposed on the primary sol-gel coating layer; the another ALD coating layer has another ALD coating layer thickness (d4) in the range of 10 to 50 nm; the separate ALD coating layer has a chemical composition that is different from a chemical composition of the primary sol-gel coating layer; 22. The luminescent material of claim 21 , wherein the another ALD coating layer comprises one or more of an oxide of one or more of Al, Zn, Hf, Ta, Zr, Ti, Sn, Nb, Y, Ga, and V.

28. the other ALD coating layer comprises another multi-layer having two or more layers with different chemical compositions; One or more of the layers may be Al 2 O 3 , TiO 2 , ZrO 2 , HfO 2 , SnO 2 , ZnO and Ta 2 O 5 and a metal oxide selected from the group consisting of 28. The luminescent material of claim 27, wherein the two or more layers have a chemical composition different from a chemical composition of the main sol-gel coating layer.

29. The first ALD layer is Al 2 O 3 and the second ALD layer comprises HfO 2 , ZrO 2 , TiO 2 , Ta 2 O 5 22. The luminescent material of claim 21, comprising one or more metal oxides selected from the group consisting of:

30. further comprising n additional ALD layers between the first ALD layer and the second ALD layer, where 2≦n≦10; each additional ALD layer has an additional ALD layer coating layer thickness (d21) in the range of 1 to 20 nm; One or more of the additional ALD layers may be HfO 2 , ZrO 2 , TiO 2 , Ta 2 O 5 22. The luminescent material of claim 21, comprising one or more metal oxides selected from the group consisting of:

31. The metal oxide of the primer layer is SiO 2 22. The luminescent material of claim 21, comprising:

32. 1. A lighting device, comprising: a wavelength converter comprising a light source configured to generate source radiation and the luminescent material of claim 21; The wavelength converter is configured to convert at least a portion of the source radiation into wavelength-converted light.

33. 33. The illumination device of claim 32, wherein the particulate luminescent material comprises an alkaline earth aluminate and the wavelength converter comprises a silicone resin.

34. 1. A display system comprising: a light emitting diode array comprising a plurality of phosphor-converted light emitting diodes, each phosphor-converted light emitting diode having a wavelength converter comprising the luminescent material of claim 21; A display and a lens or lens system spaced from the light emitting diode array and positioned to couple light from the light emitting diode array to the display; A display system comprising:

35. 1. A mobile device comprising: Camera and A flash lighting system; having 22. A mobile device, wherein the flash illumination system comprises a light emitting diode array including a plurality of light emitting diodes, each light emitting diode having a wavelength converter including the luminescent material of claim 21.

Citation Information

Patent Citations

  • Lighting system containing radiation source and fluorophore

    JP2006274265A

  • Coated luminescent particles, luminescence conversion elements, light sources, lighting devices, and methods of making coated luminescent particles

    JP2016515145A

  • Phosphors with hybrid coatings and manufacturing methods

    JP2017531068A

  • Inorganic bonding devices and structures

    JP2019537058A

  • Silicate phosphor, precursor of silicate phosphor, process for producing them and apparatus for production of precursor of silicate phosphor

    WO2005087894A1